Functionalized novolak resins, coating compositions formed therefrom, and articles and coating methods

CN123022759APending Publication Date: 2026-10-30SWIMC LLC
View PDF 42 Cites 0 Cited by

Patent Information

Application Number
CN202580024441.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-04-03
Filing Date
2025-03-07
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

相反,一些适于食品接触的已表现出良好耐腐蚀性的涂料在制造时通常表现出较差的柔韧性和不适宜的裂纹

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123022759A_ABST
    Figure CN123022759A_ABST
Patent Text Reader

Abstract

The present disclosure provides self-crosslinking novolak resins for coating compositions, coating compositions comprising such self-crosslinking novolak resins, articles having a coating formed from such compositions, and methods of coating a food or beverage packaging container or portion thereof with a coating composition herein. The food or beverage container coating compositions described herein comprise a self-crosslinking novolak resin and a second polymer capable of participating in a crosslinking reaction with the self-crosslinking novolak resin.
Need to check novelty before this filing date? Find Prior Art

Description

Cross-reference to related applications

[0001] This application claims priority to U.S. Provisional Application No. 63 / 573,797, filed April 3, 2024, pursuant to 35 USC 119(e). The entire contents of the above application are incorporated herein by reference. Technical Field

[0002] This disclosure relates to self-crosslinking phenolic varnish resins for use in coating compositions, coating compositions comprising self-crosslinking phenolic varnish resins, articles coated with coating compositions, and methods of coating using coating compositions. Background Technology

[0003] Applying coatings to metals to delay or inhibit corrosion is well-known, especially in the field of metal food and beverage containers. Coatings are typically applied to the interior of such containers to prevent food or beverage contents from contacting the metal of the container. Contact between metal and food or beverage products can, in some cases, lead to corrosion of the metal container, which can, in others, affect the packaged product. This is particularly true when the contents of the container are inherently chemically corrosive. Protective coatings are also applied to the interior of food and beverage containers to prevent corrosion, for example, in the top space of the container between the fill line and the lid, an area particularly prone to problems in some embodiments, especially for food products with high salt content. Such coatings can also advantageously be applied to the exterior of food and beverage containers to provide similar protection as needed.

[0004] A wide variety of compositions have been used to coat such surfaces of food or beverage containers. For example, roll coating or sheet coating operations are sometimes used to coat metal cans, in which a flat roll or sheet of a suitable substrate (such as steel or aluminum) is coated with a suitable composition and cured in an oven. The coated substrate can then be formed into the can end or body. Alternatively, liquid coating compositions can be applied to shaped articles by spraying, dipping, rolling, or other suitable application methods, and then cured.

[0005] Packaging coatings or container coatings should preferably be able to be applied to the substrate at high speeds and provide the necessary properties upon curing to function in these demanding end uses. For example, the coating should be food contact safe; should not adversely affect the taste of the packaged food or beverage product; should have excellent adhesion to the substrate; should be resistant to contamination and other coating defects such as “cracking,” “whitening,” and / or “bubbling”; and / or should resist degradation over long periods, even when exposed to harsh environments. Furthermore, the coating should generally be able to maintain suitable film integrity during container or packaging manufacturing and withstand the processing conditions that the container may undergo during product packaging. Additionally, the coating should have sufficient flexibility to withstand everyday can or container drop events (e.g., cans or containers falling from lower grocery store shelves) without breaking. Many current packaging coatings suffer from one or more performance defects and / or contain extractable amounts of one or more undesirable compounds, especially when the coating is exposed to short curing cycles.

[0006] Previously, various coatings have been used as internal and / or external protective tank coatings, including epoxy-based or polyvinyl chloride (PVC) coatings. However, each of these coating types has potential drawbacks. For example, the recycling of materials containing PVC or related halogenated vinyl polymers can be problematic. There is also a desire to reduce or eliminate certain BPA-based epoxy compounds and / or formaldehyde-based coatings commonly used in formulating food contact epoxy coatings, although a weighing of scientific data still suggests that the use of such materials is safe.

[0007] To address the aforementioned drawbacks, the packaging coatings industry has sought coatings based on alternative binder systems that exclude BPA-based epoxy compounds. However, formulating such coatings that exhibit a balance of desired coating properties (e.g., flexibility, adhesion, corrosion resistance, stability, crack resistance, etc.) has been problematic. For example, there is a trade-off between the corrosion resistance and manufacturability of such coatings, as well as other coating properties. For instance, some food contact coatings exhibit good manufacturability and are crack-free, but tend to be too soft and exhibit inappropriate corrosion resistance. Conversely, some food contact coatings that have demonstrated good corrosion resistance often exhibit poor flexibility and undesirable cracking during manufacturing. Summary of the Invention

[0008] This disclosure provides self-crosslinking phenolic varnish resins for use in coating compositions, coating compositions comprising such self-crosslinking phenolic varnish resins, articles having a coating formed from such compositions, and methods of coating food or beverage packaging containers or portions thereof with the coating compositions described herein.

[0009] In one embodiment, a food or beverage container coating composition is described herein, comprising: a self-crosslinking phenolic varnish resin; a second polymer capable of participating in a crosslinking reaction with the self-crosslinking phenolic varnish resin; optionally, a water-based or solvent-based liquid carrier; and wherein the food or beverage container coating composition comprises, by weight, an excess of the second polymer relative to the self-crosslinking phenolic varnish resin. In some aspects or other embodiments, the self-crosslinking phenolic varnish resin is a functionalized phenolic varnish resin, preferably a functionalized phenolic varnish resin having a protected substituent hydroxymethyl group, and most preferably, the protected substituent hydroxymethyl group comprises an alkoxymethylene substituent. In the embodiments, the functionalized phenolic varnish resin is a reaction product comprising the following reactants: (i) a phenolic varnish resin (e.g., a conventional non-self-crosslinking phenolic varnish resin obtained by reacting a phenolic compound with an aldehyde (preferably formaldehyde) under acidic conditions) and any of the following substances: (ii)(a) an aldehyde (preferably formaldehyde) and a monohydric alcohol (preferably n-butanol) or a glycol ether, using an acid catalyst, or (ii)(b) a reactive solvent (including dialkoxymethane, preferably dibutoxymethane), and preferably using an acid catalyst.

[0010] In other methods or embodiments, the food or beverage container coating composition described in the preceding paragraphs can be combined with other features or embodiments in any combination. These other features or embodiments include one or more of the following: wherein the dialkoxymethane of the reactive solvent has a structure of the following formula:

[0011] (Formula I)

[0012] Wherein R1 and R2 are independently C1 to C10 alkyl groups, C1 to C10 alkyl ether groups (e.g., alkyl groups in which one or more carbon atoms are replaced by oxygen atoms), preferably C1 to C6 alkyl groups, more preferably C2 to C5 alkyl groups, and most preferably C4 alkyl groups; and each R3 is independently hydrogen or a C1 to C6 alkyl group, and preferably each R3 is hydrogen; and / or wherein the dialkoxymethane of the reactant solvent has a boiling point of at least about 88°C and preferably about 130°C to about 305°C, and preferably wherein the dialkoxymethane is dibutoxymethane; and / or wherein (i) the conventional phenolic varnish resin is formed by reacting a phenolic compound with an aldehyde under acidic conditions (e.g., pH of about 2 or less, and preferably, pH of about 2 to about -2). Wherein, the phenolic compound is in molar excess relative to the aldehyde (e.g., the molar ratio of the phenolic compound to the aldehyde is greater than 1, and preferably from about 1 to about 3), thereby forming a phenolic varnish intermediate, and wherein the phenolic varnish intermediate is further reacted with any of the following substances: (ii)(a) an aldehyde, preferably formaldehyde and a monohydric alcohol (preferably n-butanol) or a glycol ether, or (ii)(b) a reactive solvent, including dialkoxymethane (wherein, for example, the molar ratio of dialkoxymethane to a conventional phenolic varnish resin (e.g., the molar ratio of dialkoxymethane / phenolic varnish) is at least about 0.07, at least about 0.2 in other methods, at least about 0.4 in other methods, and at least about 0.6 in yet another method); and / or wherein the exemplary functionalized phenolic varnish resin is a polymer or oligomer having the structure of Formula II:

[0013] (Formula II)

[0014] R4 is a C1 to C10 alkyl group or a C1 to C10 alkyl ether group (e.g., an alkyl group in which one or more carbon atoms are replaced by oxygen atoms), and preferably a C1 to C6 alkyl group, more preferably a C2 to C5 alkyl group, and most preferably a C4 alkyl group; and / or wherein the number average molecular weight of the functionalized phenolic varnish resin is greater than about 500 g / mol (preferably greater than about 1,000 g / mol), and more preferably less than about 4,000 g / mol (most preferably...). The concentration of phenolic compounds is less than 3,000 g / mol, as measured by gel permeation chromatography (GPC) using polystyrene standards; and / or the phenolic compounds are phenol, cresol, resorcinol, xylenol, tert-butylphenol, cyclohexylmethylphenol, dicyclopentadiene, vinylphenol, aminophenol, methoxyphenol, naphthol, cashew nut shell phenol, cashew nut bicarbonate, or combinations thereof, preferably phenol; and / or the aldehydes are formaldehyde, acetaldehyde, propionaldehyde, paraformaldehyde, butyraldehyde, glyoxal, trioxane, etc. The phenolic varnish resin comprises an alkane (e.g., a trimer of formaldehyde), hydroxybenzaldehyde (including any isomers), furfural, furfural, or combinations thereof, and preferably formaldehyde; and / or wherein the main chain of the functionalized phenolic varnish resin contains a hydrocarbon-bridged aromatic group having an alkoxymethylene substituent, and wherein the molar ratio of dialkoxymethane to conventional phenolic varnish resin (e.g., dialkoxymethane / phenolic varnish molar ratio) is at least about 0.07, at least about 0.2 in other methods, at least about 0.4 in other methods, and at least about 0.6 in yet another method; and / or wherein the hydrocarbon bridge is a methylene group; and / or wherein the main chain does not contain ether bridges between aromatic groups; and / or wherein the second polymer comprises a polyether polymer, polyester polymer, acrylic polymer, polyolefin polymer, or copolymer thereof having hydroxyl groups (preferably primary hydroxyl groups) and / or carboxyl groups for reacting with the self-crosslinking phenolic varnish resin; and / or wherein the acid value of the second resin is at least about 0 mg. The KOH / g resin, and preferably from about 0 mg KOH / g resin to about 150 mg KOH / g resin; and / or wherein the hydroxyl value of the second resin is at least about 15 mg KOH / g resin, and preferably from about 20 mg KOH / g resin to about 200 mg KOH / g resin; and / or wherein the food or beverage container coating composition is substantially free of each of bisphenol A and bisphenol S (and preferably free of either of them); and / or wherein the neutralized self-crosslinking phenolic varnish resin (e.g., pH greater than 4).0) Stable at room temperature (e.g., from about 20°C to about 25°C) for at least about 90 days, wherein the viscosity change is an increase of less than 100% relative to the viscosity at time T0, and preferably, the viscosity change is an increase of about 0% to less than 50% relative to the viscosity at time T0, wherein the viscosity is measured according to ASTM D2983; and / or wherein the coating composition is applied to tinplate (ETP) and cured at 200°C for 10 minutes to achieve 4 mg / in. 2 Up to 8mg / in 2 At the dry film thickness, as measured according to ASTM D5402, it exhibits at least about 50 MEK bi-friction cycles; and / or wherein the coating composition comprises about 5% to about 50% by weight of a self-crosslinking phenolic varnish resin (preferably about 15% to about 35% by weight) and about 50% to about 95% by weight of a second polymer (preferably about 60% to about 80% by weight); and / or wherein, based on the total resin solids comprising the self-crosslinking phenolic varnish resin, the coating composition comprises about 5% to about 35% by weight of a reactive solvent, including dialkoxymethane; and / or wherein the coating composition comprises less than about 1,000 ppm of free formaldehyde, preferably less than 500 ppm of formaldehyde, and most preferably less than 100 ppm of free formaldehyde; and / or further comprises a lubricant; and / or wherein the lubricant is selected from carnauba wax, polyvinyl wax, Fischer-Tropsch wax, fatty acid ester wax, silicone wax, lanolin wax, hydroxyl-functionalized polysiloxane wax, or others. The coating composition comprises, if applicable, a combination of the following: and / or wherein the coating composition contains at least about 25% by weight water; and / or wherein the coating composition further comprises one or more water-miscible organic solvents; and / or wherein the water-miscible organic solvents include isopropanol, ethanol, methanol, butanol, pentanol, glycol, glycol ether, glycol ester, acetone, methyl ethyl ketone, tetrahydrofuran, or mixtures thereof; and / or wherein the coating composition contains about 3.5% by weight to about 15% by weight of one or more water-miscible organic solvents; and / or wherein the coating composition contains at least about 5% by weight of one or more organic solvents; and / or wherein, when tested according to a total extraction test, the food or beverage container coating composition forms a cured coating containing less than 50 ppm of extractable material, if applicable; and / or wherein the food or beverage container coating composition contains about 15% by weight to about 40% by weight of total resin solids (preferably about 18% by weight to about 35% by weight, and more preferably about 20% by weight to about 30% by weight).

[0015] In other methods or embodiments, this document describes an article that constitutes a food or beverage container or a portion thereof. In one aspect, the article comprises a metal substrate; and a thermosetting coating disposed on at least a portion of the metal substrate, wherein the thermosetting coating is derived from a food or beverage coating composition as described in any embodiment or method of this invention. In other embodiments, the thermosetting coating is formed by baking a food or beverage coating composition of any embodiment of this invention at a temperature of at least about 135°C. In other embodiments, any embodiment of the food or beverage coating composition of this invention is applied to a food or beverage contact surface of a metal substrate.

[0016] In other methods or embodiments, this document describes a method of forming a food or beverage container. In one aspect, the method includes a food or beverage coating composition according to any embodiment of the present invention; and applying the food or beverage coating composition to the metal substrate or a portion thereof before or after forming a metal substrate into a food or beverage container or a portion thereof. In another embodiment, the method includes baking and curing the food or beverage coating composition after it has been applied to the metal substrate.

[0017] In other methods or embodiments, this document also describes a method of applying a coating composition of any embodiment of the present invention to a metal substrate of a food or beverage container or a portion thereof and / or using a coating composition of any embodiment of the present invention on a metal substrate of a food or beverage container or a portion thereof.

[0018] The above description of the invention is not intended to describe every disclosed embodiment or every specific implementation of the invention. The following description illustrates exemplary embodiments in more detail. Guidance is provided in several places throughout this application by way of a list of examples, which may be used in various combinations. In each case, the cited list is used only as a representative group and should not be construed as an exclusive enumeration. Details of one or more embodiments of the invention are set forth in the following description. Other features, objectives, and advantages of the invention will become apparent from the specification and claims. Attached Figure Description

[0019] Figure 1 The graph shows the storage modulus of coating compositions over time, which contain an acrylic or epoxy second polymer in combination with a first resin in a phenolic varnish DBM pre-reaction crosslinking system or a phenolic varnish DBM blend crosslinking system.

[0020] Selected definition

[0021] Unless otherwise specified or obvious from the context, the following terms as used herein have the meanings provided below.

[0022] Unless otherwise specified, references to "(meth)acrylate" compounds (where "methyl" is enclosed in parentheses) are abbreviated references to both acrylate compounds and methacrylate compounds.

[0023] As used herein, the term "organic group" means a hydrocarbon group (having an optional element other than carbon and hydrogen, such as oxygen, nitrogen, sulfur, and silicon) classified as an aliphatic group, a cyclic group, or a combination of aliphatic and cyclic groups (e.g., alkylaryl groups and aralkyl groups). The term "aliphatic group" means a saturated or unsaturated straight-chain or branched hydrocarbon group. For example, this term is used to encompass alkyl groups, alkenyl groups, and alkynyl groups. The term "alkyl group" means a saturated straight-chain or branched hydrocarbon group, including, for example, methyl, ethyl, isopropyl, tert-butyl, heptyl, dodecyl, octadecyl, pentyl, 2-ethylhexyl, etc. The term "alkenyl group" means an unsaturated, straight-chain or branched hydrocarbon group having one or more carbon-carbon double bonds, such as a vinyl group. The term "cyclic group" means a closed-ring hydrocarbon group classified as an alicyclic group or an aromatic group, both of which may contain heteroatoms.

[0024] Groups that may be the same or different are referred to as something “independently.” The organic group intended to replace the compound disclosed herein is intended to replace it. As a means of simplifying the discussion and expression of certain terms used in this application, the terms “group” and “part” are used to distinguish between chemical species that are permitted to be substituted or can be substituted and those that are not permitted to be substituted or can not be so substituted. Thus, when the term “group” is used to describe a chemical substituent, the described chemical substance includes unsubstituted groups, as well as those groups having, for example, O, N, Si, or S atoms in the chain (such as in an alkoxy group) and carbonyl groups or other conventional substitutions. When the term “part” is used to describe a chemical compound or substituent, it is intended to include only unsubstituted chemical substances. For example, the phrase “alkyl group” is intended to include not only pure open-chain saturated hydrocarbon alkyl substituents, such as methyl, ethyl, propyl, tert-butyl, etc., but also alkyl substituents having other substituents known in the art, such as hydroxyl, alkoxy, alkylsulfonyl, halogen atom, cyano, nitro, amino, carboxyl, etc. Therefore, "alkyl group" includes ether groups, haloalkyl groups, nitroalkyl groups, carboxyalkyl groups, hydroxyalkyl groups, sulfonalkyl groups, etc. On the other hand, the phrase "alkyl moiety" is limited to containing only pure open-chain saturated hydrocarbon alkyl substituents, such as methyl, ethyl, propyl, tert-butyl, etc.

[0025] The term "component" refers to any compound that contains specific features or structures. Examples of components include compounds, monomers, oligomers, polymers, and the organic groups contained therein.

[0026] The term "olefinic unsaturation" refers to compounds containing non-aromatic carbon-carbon double bonds (i.e., -C=C-), wherein vinyl double bonds are preferred.

[0027] When used with respect to coating compositions that may contain a specific compound, the term "substantially free of" means that the coating composition contains less than 1,000 parts per million (ppm) of the compound (corresponding to less than 0.1% by weight), regardless of the form of the compound. When used with respect to coating compositions that may contain a specific compound, the term "substantially free of" means that the coating composition contains less than 100 parts per million (ppm) of the compound, regardless of the form of the compound. When used with respect to coating compositions that may contain a specific compound, the term "substantially completely free of" means that the coating composition contains less than 5 parts per million (ppm) of the compound, regardless of the form of the compound. When used with respect to coating compositions that may contain a specific compound, the term "completely free of" means that the coating composition contains less than 20 parts per billion (ppb) of the compound, regardless of the form of the compound. When the phrases "free of" (outside the context of the above phrases), "do not contain / does not contain," "does not include any," etc., are used herein, such phrases are not intended to exclude the presence of trace amounts of the relevant structure or compound that may be present but not intentionally used, such as the presence of environmental pollutants. As will be understood by those skilled in the art, the amount of compounds in an ingredient, polymer, formulation, or other component can generally be calculated based on the amount of starting material used and the yield obtained when preparing such an ingredient, polymer, formulation, or other component. The term "food contact surface" refers to the surface of an article (e.g., a food or beverage container) that comes into contact with, or is suitable for, a food or beverage product. When used in the context of a coating composition applied to a food contact surface of a packaged article (e.g., a food or beverage container), the term refers to the underlying substrate to which the coating composition is applied (typically associated with the inner surface of the packaged article) and does not imply that the lower portion of the substrate will come into contact with the food or beverage product.

[0028] When used in the context of coatings applied to a surface or substrate, the term "on" includes coatings applied directly or indirectly to the surface or substrate. Thus, for example, a coating applied to a primer layer covering a substrate constitutes a coating applied to the substrate.

[0029] Unless otherwise specified, the terms "polymer" and "polymeric material" include, but are not limited to, homopolymers, copolymers (such as, for example, block, graft, random or statistical and alternating copolymers, terpolymers, etc.), and blends and modifications thereof. Furthermore, unless otherwise specifically limited, the term "polymer" should include all possible geometries of the material. These geometries include, but are not limited to, isotactic, syndiotactic, and random symmetry. Typically, polymers have a number-average molecular weight of about 1,000 g / mol or greater. Also as used herein, "oligomer" refers to a polymer with a lower molecular weight and typically has a number-average molecular weight of less than about 1,000 g / mol. As used herein, the term "resin" refers to a composition comprising both a polymer and / or an oligomer.

[0030] The term "monomer unit" refers to a structural unit produced by the polymerization of monomers. As used herein, "monomer" or reactant generally refers to a compound within the reaction mixture prior to polymerization, and a monomer unit or (alternatively) a structural unit refers to a monomer or reactant within the polymer. If the discussion herein refers to monomers or reactants, it also means the resulting monomer units, structural units, or repeating units thereof in the polymer. Similarly, if the discussion refers to monomer units, structural units, or repeating units, it also means the mixture of monomers or reactants used to form a polymer having associative units therein.

[0031] As used herein, a "crosslinker" refers to a molecule or compound capable of forming covalent bonds between polymers or between two different regions of the same polymer. Self-crosslinking refers to the ability of a molecule or compound to form such covalent bonds without the need for a curing agent. Self-crosslinking compounds can form such covalent bonds or bonds simply by applying heat. The preferred self-crosslinking functionalized phenolic varnish resins described herein are capable of self-crosslinking under typical thermosetting baking conditions for coatings used in food or beverage containers (e.g., oven temperatures of 170°C to 240°C and curing times of 1 minute to 30 minutes).

[0032] When used in the context of “protected hydroxymethyl group”, the term “protected” encompasses both of the following: (i) a hydroxymethyl group (i.e., -CH2-OH) that has been protected with a capping agent (e.g., n-butanol) to prevent premature consumption of the hydroxymethyl group before heat curing (e.g., irreversible reaction), such that the hydroxymethyl group can be used to participate in crosslinking reactions during heat curing conditions (e.g., oven baking temperatures of 170°C to 230°C) commonly used to cure coating compositions for food or beverage containers; and (ii) an alkoxymethylene group that is not necessarily provided via a reaction involving the formation of the hydroxymethyl group, but which produces a hydroxymethyl group that can be used to participate in crosslinking reactions during heat curing conditions (e.g., oven baking temperatures of 170°C to 230°C) commonly used to cure coating compositions for food or beverage containers.

[0033] In the context of “substituent hydroxymethyl group”, the term “substituent” refers to a hydroxymethyl group that is directly attached to an atom of an aryl ring. For example, a hydroxymethyl group in which the carbon of the hydroxymethyl group is directly attached to a carbon of a benzene ring is a substituent hydroxymethyl group. Similarly, when used in the context of “substituent-protected hydroxymethyl group”, the term “substituent” refers to a protected hydroxymethyl group in which the methylene carbon of the protected hydroxymethyl group is directly attached to a carbon of a benzene ring.

[0034] As discussed in more detail below, the functionalized phenolic varnish resins of this article are stable at room temperature (e.g., from about 20°C to about 25°C) for at least about 90 days. As used herein, “stable” means a composition in which the viscosity increases by no more than 100% relative to the initial viscosity at time T0, and preferably the viscosity change is an increase of about 0% to less than 50% relative to the initial viscosity at time T0, wherein the viscosity is measured at room temperature on a Brinell viscometer, and the rotor size and rpm are selected according to the parameters of ASTM D2983. (For example, if the initial viscosity is 100 cPs, an increase in viscosity to less than 200 cPs is acceptable, while an increase in viscosity to more than 200 cPs is unacceptable).

[0035] The term "comprising" and its variations are not intended to be limiting when they appear in the specification and claims.

[0036] The terms "preferred" and "ideally" refer to embodiments of the invention that provide certain beneficial effects in certain circumstances. However, other embodiments may also be preferred in the same or other circumstances. Furthermore, the description of one or more preferred embodiments does not imply that other embodiments are unavailable, and is not intended to exclude other embodiments from the scope of the invention.

[0037] As used herein, unless otherwise expressly stated otherwise, the term "or" is generally used in its conventional meaning, including "and / or".

[0038] As used herein, the terms “an,” “a,” “the,” “at least one,” and “one or more” are used interchangeably. Thus, for example, a coating composition containing “an” additive can be interpreted as meaning that the coating composition contains “one or more” additives.

[0039] Similarly, throughout this document, all numerical values ​​are assumed to be modified by the term “about,” and in some embodiments, preferably by the term “precisely.” As used herein in conjunction with the quantity being measured, the term “about” refers to a variation in the quantity being measured, as would be expected by a technician performing the measurement and applying a level of care commensurate with the purpose of the measurement and the accuracy of the measuring equipment used. In this document, a “maximum” value (e.g., up to 50) includes that value (e.g., 50).

[0040] Furthermore, in this document, the numerical range expressed by endpoints includes all numerical values ​​contained within that range (e.g., 1 to 5 includes 1, 1.5, 2, 2.75, 3, 3.80, 4, 5, etc.). In addition, disclosure of a range includes disclosure of all subranges included in a wider range (e.g., 1 to 5 discloses 1 to 4, 1.5 to 4.5, 1 to 2, etc.). Detailed Implementation

[0041] Conventional phenolic varnish resins do not self-crosslink under the heat baking conditions typically used in conjunction with food or beverage container coating compositions. For such conventional phenolic varnish resins to initiate a crosslinking reaction, the presence of an additional curing agent that reacts with the phenolic varnish resin is required, such as, for example, methylphenolic resins, amino resins (urea-formaldehyde, melamine-formaldehyde and their derivatives, such as benzoquinone), and formaldehyde resins and their derivatives (such as hexamethylenetetramine, trioxane, and paraformaldehyde), all of which are formaldehyde-based resins. Furthermore, high-functionality epoxy resins can also be used to cure conventional phenolic varnish resins. In one aspect, this disclosure provides a functionalized phenolic varnish resin that can be used in coating compositions and is capable of crosslinking without the need for the addition of a curing agent. Specifically, this disclosure provides self-crosslinking phenolic varnish resins, food or beverage container coating compositions comprising such resins, and food or beverage containers (or portions thereof) coated with such compositions. The unique phenolic varnish resins of this disclosure are suitable for food or beverage container coating compositions, articles having a coating formed from such coating compositions, and methods of coating food or beverage containers with coating compositions. In this document, the term "food or beverage container" is used to encompass containers used for food or beverage products, including, but not limited to, metal beverage cups and one-, two-, or three-piece containers (including, but not limited to, the conical recycled aluminum cups described in US 10,875,076), metal food containers other than conventional food or beverage cans (e.g., two-piece stretch food cans, three-piece food cans, food can ends, stretch-flattened cans, beverage can ends, etc.), and metal closures for glass food or beverage containers. All such containers are eligible for coating with the food or beverage container coating compositions disclosed herein.

[0042] In one method or embodiment, a food or beverage container coating composition is provided, comprising at least: a self-crosslinking phenolic varnish resin; a second polymer capable of participating in a crosslinking reaction with the self-crosslinking phenolic varnish resin (e.g., without the need for conventional phenolic varnish curing agents and curing solely by applying heat); optionally, a water-based or solvent-based liquid carrier; and wherein the food or beverage container coating composition comprises an excess of the second polymer relative to the self-crosslinking phenolic varnish resin by weight. As discussed in more detail herein, the self-crosslinking phenolic varnish resin is a functionalized phenolic varnish resin, preferably a functionalized phenolic varnish resin having a protected substituent hydroxymethyl group, and most preferably, wherein the protected substituent hydroxymethyl group comprises an alkoxymethylene substituent. In a preferred method, the suitable functionalized phenolic varnish resin described herein is a reaction product of the following substances using an acidic catalyst: (i) a conventional phenolic varnish resin (e.g., formed by reacting a phenolic compound with an aldehyde (preferably formaldehyde)) and any of the following substances: (ii) (a) an aldehyde (preferably formaldehyde) and a monohydric alcohol or glycol ether, or (ii) (b) a reactive solvent, including dialkoxymethane. Preferably, the functionalized phenolic varnish resin is formed by reacting a conventional phenolic varnish resin and a reactive solvent using an acidic catalyst.

[0043] Self-crosslinking phenolic varnish resin

[0044] Conventional phenolic varnish resins do not self-crosslink, and any crosslinking that occurs in conventional phenolic varnish resins only happens with the use of an external crosslinking agent (e.g., a curing agent as described below). As understood, conventional phenolic varnish resins include resins formed by the reaction of phenolic compounds (e.g., phenol, BPA, BPF, etc., discussed in more detail below) and aldehydes (e.g., formaldehyde, etc., discussed in more detail below) under specific reaction conditions. For example, conventional phenolic varnish resins employ acid catalysis, wherein the molar ratio of aldehyde to phenol is less than 1.0 (or conversely, the molar ratio of phenol to aldehyde is greater than 1.0).

[0045] In contrast, the self-crosslinking phenolic varnish resins of this disclosure include functionalized phenolic varnish resins, and more specifically, functionalized phenolic varnish resins having protected substituent hydroxymethyl groups, and most preferably, the protected substituent hydroxymethyl groups comprising alkoxymethylene groups. To promote crosslinking, the phenolic varnish resin preferably comprises a plurality of such protected substituent hydroxymethyl groups. As previously discussed, the term "protected substituent hydroxymethyl groups" does not require such groups to be prepared via a process utilizing hydroxymethyl groups in an intermediate step, although some embodiments do use such a process to generate such groups. The term also refers to groups (e.g., alkoxymethylene groups) capable of providing hydroxymethyl groups during the thermosetting conditions conventionally used for curing food can coatings. In one method, the functionalized phenolic varnish resin of this article comprises a reaction product of the following components, which include (i) a conventional phenolic varnish resin (e.g., formed by reacting a phenolic compound with an aldehyde (preferably formaldehyde) under acidic conditions as described above) and any of the following substances: (ii)(a) an aldehyde (preferably formaldehyde) and a monohydric alcohol or glycol ether using an acid catalyst, or (ii)(b) a reactive solvent (including dialkoxymethane) using an acid catalyst.

[0046] More specifically, conventional phenolic varnish resins suitable as starting reactants for forming the self-crosslinking phenolic varnishes described herein can be formed by reacting a phenolic compound and an aldehyde under acidic conditions with the phenolic compound in molar excess relative to the aldehyde, thereby forming a phenolic varnish intermediate. As used herein, acidic conditions include reactions with a pH of about 2 or less, and preferably a pH of about 2 to about -2, and a molar excess of the phenolic compound means a molar ratio of the phenolic compound to the aldehyde greater than 1, and preferably about 1 to about 3. Conventional phenolic varnish resins can be formed using acid catalysts, including but not limited to strong inorganic acids (e.g., sulfuric acid, phosphoric acid, and / or hydrochloric acid) and strong organic acid catalysts (such as oxalic acid, p-toluenesulfonic acid) and inorganic salts (such as zinc acetate, zinc borate, etc.). Conventional phenolic varnish resins are thermoplastic polymers that can be melted by applying heat alone, but do not crosslink; crosslinking only occurs with the addition of a phenolic varnish curing agent.

[0047] Suitable phenolic compounds for forming the starting (e.g., conventional) phenolic varnish resins described herein include phenol, cresol, resorcinol, xylenol, tert-butylphenol, cyclohexylmethylphenol, dicyclopentadiene, vinylphenol, methoxyphenol, naphthol, cashew nut shell powder, cashew nut biol, or combinations thereof. Preferably, the phenolic compound for forming the conventional phenolic varnish resins described herein is phenol, cresol, or mixtures thereof. Suitable aldehyde reactants for forming the starting (e.g., conventional) phenolic varnish resins include formaldehyde, acetaldehyde, propionaldehyde, paraformaldehyde, butyraldehyde, glyoxal, trioxane (e.g., a trimer of formaldehyde), hydroxybenzaldehyde (including any isomers), furfural, furfural, or combinations thereof. Preferably, the aldehyde compound for forming the conventional phenolic varnish resins described herein is formaldehyde.

[0048] Suitable phenolic varnish resins for forming the functionalized phenolic varnish resins of this disclosure are readily commercially available. Examples of such commercially available conventional phenolic varnish resins include Alnovol PN320 phenolic varnish resin product available from Allnex, HRJ 12952 phenolic varnish resin product available from SI Group, Durite SD1708 phenolic varnish resin product available from Bakelite Synthesis, and Durite SD1731 phenolic varnish resin product available from Bakelite Synthetics.

[0049] The intermediate reaction product is then preferably further reacted via one of two pathways to functionalize the formed or commercially available phenolic varnish intermediate (e.g., conventional phenolic varnish resin) into a cost-disclosed self-crosslinking phenolic varnish resin: (ii)(a) by reacting the intermediate with an additional aldehyde (preferably formaldehyde) and a monohydric alcohol or glycol ether using an acid catalyst, or (ii)(b) by using a reactive solvent (including dialkoxymethane compounds) and an acid catalyst. For pathway (ii)(b), preferably, the intermediate is reacted with a reactive solvent (including dialkoxymethane compounds) and an acid catalyst. The reaction in pathway (ii)(b) can occur at any suitable time, including, for example, during the following periods: (i) formation of a functionalized phenolic varnish resin for subsequent formulation into a coating composition, (ii) thermosetting of a coating composition comprising a reactive solvent and an intermediate and preferably an acid catalyst, or (iii) both (i) and (ii). The resulting functionalized or self-crosslinking phenolic varnish resin can be crosslinked with the second polymer as described herein without the need for common phenolic varnish curing agents, and preferably, can be self-crosslinked to the second polymer herein simply by applying heat (such as curing temperatures of about 130°C to about 300°C, 175°C to about 250°C in other methods, and 180°C to about 220°C in yet another method). As used herein, "not requiring conventional phenolic varnish curing agents" means that the compositions herein are substantially free of (and preferably free of) or contain no formaldehyde curing agents, paraformaldehyde curing agents, hexamethylenetetramine (HMTA) curing agents, combinations thereof, or similar curing agents typically used with conventional phenolic varnish resins.

[0050] In one method or embodiment, the reactive solvent suitable for forming the self-crosslinking phenolic varnish resin described in pathway (ii)(b) above comprises a selected dialkoxymethane compound whose molecular weight and boiling point are suitable for functionalizing conventional phenolic varnish resins into self-crosslinking phenolic varnish resins using an acidic catalyst (such as a strong acid). In a preferred embodiment, the dialkoxymethane of the reactive solvent has the structure of Formula I:

[0051] (Formula I)

[0052] In Formula I, R1 and R2 are independently C1 to C10 alkyl groups or C1 to C10 alkyl ether groups (e.g., alkyl groups in which one or more carbon atoms are replaced by oxygen atoms). Preferably, each R1 and R2 is independently C1 to C6 alkyl groups, more preferably C2 to C5 alkyl groups, and most preferably C4 alkyl groups. Each R3 in Formula I is independently hydrogen or a C1 to C6 alkyl group, and preferably each R3 is hydrogen. The preferred reactant solvent, dialkoxymethane, has a molecular weight of about 100 g / mol to about 200 g / mol, preferably about 130 g / mol to about 190 g / mol, and a boiling point of at least about 88°C and preferably about 88°C to 305°C, or about 130°C to about 250°C, or about 160°C to about 225°C, or about 170°C to about 200°C. Suitable dialkoxymethanes include diethoxymethane (DEM) with a molecular weight of 104.15 and a boiling point of 88°C, dipropoxymethane (DPM) with a molecular weight of 132.20 and a boiling point of 141°C, dibutoxymethane (DBM) with a molecular weight of 160.26 and a boiling point of 179°C, dipentoxymethane (DPTM), and / or di(butoxyethoxy)methane (DBEM) or combinations thereof. In one embodiment, a preferred reactive solvent includes dibutoxymethane. In one embodiment herein, the food or beverage container coating composition comprises about 5% to about 35% by weight of a reactive solvent, including dialkoxymethane, based on the total resin solids comprising a self-crosslinking phenolic varnish resin. In another embodiment, the molar ratio of dialkoxymethane to conventional phenolic varnish resin in the food or beverage container coating composition (e.g., the molar ratio of dialkoxymethane / phenolic varnish) is at least about 0.07, at least about 0.2 in other methods, at least about 0.4 in still other methods, and at least about 0.6 in yet another method.

[0053] In other methods or embodiments, the functionalization of the above-described pathway (ii)(a) suitable for forming the self-crosslinking phenolic varnish described herein involves reacting a conventional phenolic varnish intermediate with a reaction mixture comprising a reactant of an aldehyde (preferably formaldehyde), a monohydric alcohol or glycol ether, and an acidic catalyst (such as a strong acid). Examples of suitable monohydric alcohols include ethanol, propanol, butanol, pentanol, and similar monohydric alcohols or combinations thereof. Examples of suitable glycol ethers include methoxyethanol, ethoxyethanol, propoxyethanol, isopropoxyethanol, butoxyethanol, phenoxyethanol, benzyloxyethanol, and similar glycol ethers.

[0054] Examples of suitable acid catalysts for any functionalization pathway include strong acids, such as strong inorganic acids (e.g., sulfuric acid, phosphoric acid, and / or hydrochloric acid), strong organic acid catalysts (e.g., oxalic acid, p-toluenesulfonic acid), and inorganic salts (e.g., zinc acetate, zinc borate, etc.). Such functionalization reactions can occur at temperatures ranging from about 50°C to about 100°C, preferably from about 55°C to about 90°C, and most preferably from about 60°C to about 85°C.

[0055] In the embodiments or methods, the functionalized phenolic varnish resin (e.g., a conventional phenolic varnish reacted via either route (ii)(a) using a reaction mixture of an aldehyde (preferably formaldehyde) and a monohydric alcohol or glycol ether, or alternatively via route (ii)(b) using a reactive solvent (including dialkoxymethane)) is, in one embodiment, a resin (e.g., a polymer or oligomer) that at least partially comprises the general structure of Formula II:

[0056] (Formula II)

[0057] The polymer backbone of the polymer or oligomer has repeating aromatic groups, which are bridged by alkylene groups (typically methylene), and the aromatic groups include protected substituents, such as protected substituent hydroxymethyl groups, and most preferably, the protected substituent hydroxymethyl groups include alkoxymethylene substituents (e.g., -CH2OR4 groups). In one method, the substituent hydroxymethyl groups as shown in Formula II above include R4 groups, which are C1 to C10 alkyl groups or C1 to C10 alkyl ether groups (e.g., alkyl groups in which one or more carbon atoms are replaced by oxygen atoms). Preferably, the R4 groups include C1 to C6 alkyl groups, more preferably C2 to C5 alkyl groups, and most preferably C4 alkyl groups. In a preferred embodiment, the functionalized phenolic varnish resin of this article has a number average molecular weight greater than about 500 g / mol, preferably greater than about 750 g / mol, and most preferably greater than 1,000 g / mol. In other embodiments, the number-average molecular weight of the functionalized phenolic varnish resin described herein is less than about 4,000 g / mol, preferably less than about 3,500 g / mol, and more preferably less than 3,000 g / mol. The number-average molecular weight used herein was measured using polystyrene standards by gel permeation chromatography (GPC).

[0058] More specifically, the functionalized phenolic varnish resins formed herein are resins (e.g., polymers or oligomers) whose main chain comprises hydrocarbon-bridged aromatic groups having alkoxymethylene substituents, and the molar ratio of alkoxymethane to phenolic varnish is as discussed above. In one method, the hydrocarbon bridges or linking groups between adjacent aromatic groups in the main chain are preferably methylene groups as shown above with respect to Formula II. Most preferably, the main chain is substantially free of ether bridges between aromatic groups.

[0059] In the embodiments, the hydroxymethyl or hydroxymethyl ether group of Formula II above is attached to the ortho or para position of the phenolic ring, and most preferably, as shown in Formula II above, to the para position of the phenolic ring (all relative to the hydroxyl group). As will be understood by those skilled in the art, the hydroxymethyl substitution on the phenolic ring can be determined by 13C NMR and similar analytical techniques.

[0060] In embodiments, the protected substituent hydroxymethyl group includes an alkoxymethylene substituent (e.g., a -CH2OR4 group), which can be formed in situ during curing. In one method, the substituent hydroxymethyl group (e.g., the protected substituent hydroxymethyl group) includes an R4 group, which is a C1 to C10 alkyl group or a C1 to C10 alkyl ether group (e.g., an alkyl group in which one or more carbon atoms are replaced by oxygen atoms). Preferably, the R4 group includes a C1 to C6 alkyl group, more preferably a C2 to C5 alkyl group, and most preferably a C4 alkyl group. In some methods, the protected substituent hydroxymethyl group can be formed in situ during coating curing.

[0061] In the embodiments described herein, the functionalized phenolic varnish resin is stable at room temperature (e.g., from about 20°C to about 25°C) for at least about 90 days, wherein the stability is manifested in minimal viscosity change of the functionalized phenolic varnish resin, i.e., a viscosity increase of less than 100% relative to the viscosity at time T0, and preferably, the viscosity change is a viscosity increase of about 0% to less than 50% relative to the viscosity at time T0, wherein the viscosity is measured by ASTM D2983 (e.g., rotor selection and rpm). (e.g., if the initial viscosity is 100 cPs, a viscosity increase to below 200 cPs is acceptable, while a viscosity increase to more than 200 cPs is unacceptable).

[0062] In embodiments, the phenolic varnish resin described herein is prepared according to a molar ratio of dialkoxymethane component to conventional phenolic varnish resin component (e.g., dialkoxymethane / phenolic varnish) of at least about 0.07, at least about 0.2 in other methods, at least about 0.4 in other methods, and at least about 0.6 in yet another method. In other embodiments, the phenolic varnish resin may individually and preferably comprise one or more optional monomers or monomer units, including but not limited to olefinically unsaturated monomers such as, for example, (meth)acrylates (e.g., alkyl, cycloalkyl, alkoxy, and aromatic (meth)acrylates), vinyl esters of saturated carboxylic acids, monoolefins, conjugated dienes, styrene, (meth)acrylamide, hydroxymethyl (meth)acrylamide, styrene, α-methylstyrene, vinyltoluene, vinyl propionate, vinyl acetate, acrylonitrile, vinyl chloride (halogen-containing monomers are not currently preferred), etc. In one embodiment, other monomers may include one or more polyfunctional (meth)acrylate monomers. In some embodiments, other monomers also include one or more olefinically unsaturated carboxyl-functionalized amide monomers, such as ureidofunctionalized monomers, such as monomers formed as reaction products between aminoalkylalkylene ureas (e.g., aminoethylene urea) and olefinically unsaturated carboxylic acids or anhydrides (e.g., maleic anhydride). Examples of suitable (meth)acrylates and (meth)acrylate monomers include acrylic acid, methacrylic acid, methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, cyclohexyl acrylate, benzyl acrylate, methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, 2-ethylhexyl methacrylate, hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxybutyl acrylate, hydroxybutyl methacrylate, cyclohexyl methacrylate (CHMA), glycidyl methacrylate, 4-hydroxybutyl acrylate glycidyl ether, allyl methacrylate, and mixtures thereof. Preferred optional monomers include styrene, methyl methacrylate, ethyl acrylate, methacrylic acid, n-butyl acrylate, tert-butyl acrylate, tert-butyl methacrylate, n-butyl methacrylate, itaconic acid esters, vinyl acetate, 2-ethylhexyl acrylate, CHMA, bio-based monomers, etc. Suitable polyene-bonded unsaturated monomers include polyfunctional acrylates, such as difunctional, trifunctional, and tetrafunctional acrylates.

[0063] In other embodiments, optional additional monomers may also include one or more bio-based monomers. As used herein with respect to monomers, “bio-based” refers to a monomer preferably obtained from biorenewable olefinically unsaturated monomers. Such biorenewable olefinically unsaturated monomers have a significantly higher C-14 (C-14) content than olefinically unsaturated monomers derived from fossil fuels. C-14 has a relatively short half-life on an epoch-scale in fossil fuel-based materials and is therefore present in lower amounts in fossil fuel-based materials relative to bio-based materials. Thus, as used herein, “biorenewable” olefinically unsaturated monomers mean monomers with C-14 isotope levels comparable to the average level of C-14 in atmospheric CO2, as measured by ASTM D6866; or having at least about 1.5 dpm / gC (decays per gram of carbon per minute), at least 2.5 dpm / gC, or at least 3.0 dpm / gC, as measured by liquid scintillation counting. Exemplary examples of such bio-based monomers include esters of itaconic acid, bio-derived (meth)acrylic acid or esters thereof, and alkyl (meth)acrylic acid or esters thereof. In an embodiment, the bio-based monomers constitute at least 10%, at least 20%, at least 30%, or at least 40% by weight of the vinyl methyl phenolic resin, based on the total weight of all monomers polymerized to form the vinyl methyl phenolic resin.

[0064] The monomeric components do not need to be arranged in any particular order in the self-crosslinking phenolic varnish resin described herein. The monomers of the phenolic varnish resin can be polymerized such that the monomeric components are randomly distributed in segments or repeating blocks (block copolymers) or in other arrangements (forming statistical copolymers).

[0065] Optional liquid carrier :

[0066] In some embodiments, the food or beverage container coating compositions described herein also include an optional water-based or organic solvent-based liquid carrier. In a preferred embodiment, the carrier is a liquid solvent capable of dissolving or dispersing the self-crosslinking phenolic varnish resin and / or the second polymer. In a further preferred embodiment, the solvent is a protic solvent such as an alcohol (e.g., butanol, carbitol) and a glycol, a cyclic or acyclic ether such as tetrahydrofuran (THF), di(propylene glycol) dimethyl ether, or a mixture of isomers (e.g., isomers of ether solvents as described in CAS No. 111109-77-4), or a mixture thereof. In embodiments, the carrier liquid may include water. In some embodiments, the coating composition is an aqueous coating composition which may optionally contain one or more water-miscible organic solvents. In other embodiments, the coating composition is an organic solvent-based coating composition.

[0067] In some embodiments, the food or beverage container coating compositions described herein are provided in a liquid-free form. The self-crosslinking phenolic varnish resins described herein are anticipated to be useful when added as solids or semi-solids to coating compositions or in other non-liquid coating application techniques, such as, for example, powder coating, extrusion coating, or lamination, where a liquid carrier may be optional. In some embodiments, the self-crosslinking phenolic varnish resins described herein are spray-dried to form a powder, which can then be electrostatically applied to a substrate (e.g., as described in U.S. Patent No. 11,248,127, the entire contents of which are incorporated herein by reference).

[0068] In preferred embodiments, the self-crosslinking phenolic varnish resins and / or food or beverage container coating compositions herein are substantially free of, more preferably substantially free of, more preferably substantially completely free of, and optionally completely free of formaldehyde (i.e., free formaldehyde), phenol (i.e., free phenol), bisphenol A (“BPA”), bisphenol F (“BPF”), bisphenol S (“BPS”), and epoxides of BPA, BPF, and BPS, or at least one of them. In some preferred embodiments, the self-crosslinking phenolic varnish resins are free of any BPA, BPF, BPS, or epoxides of BPA, BPF, and BPS. In preferred embodiments, the monomer components used to prepare the self-crosslinking phenolic varnish resins herein do not include glycidyl acrylate or glycidyl methacrylate. In some embodiments, the self-crosslinking phenolic varnish resins do not contain any ethylene oxide functional groups. In other methods, the self-crosslinking phenolic varnish resins are preferably prepared without the use of any halogenated monomers (e.g., vinyl chloride). More preferably, the self-crosslinking phenolic varnish resins do not contain any halogen atoms.

[0069] Second polymer

[0070] The food or beverage container coating compositions described herein may also contain a second polymer capable of participating in a crosslinking reaction with the self-crosslinking phenolic varnish resin described herein, without the need for conventional phenolic varnish curing agents (e.g., substantially free of the conventional curing agents discussed above). That is, crosslinking can occur solely by applying heat or baking (such as temperatures from about 130°C to about 200°C, or from about 175°C to about 220°C, or preferably from 180°C to about 250°C).

[0071] A variety of second polymers commonly used in the container coatings industry can be used in the compositions disclosed herein. These include, for example, polyether polymers, polyester polymers (including, for example, polyester polyurethanes), acrylic polymers, polyolefin polymers, copolymers having hydroxyl groups (preferably primary hydroxyl groups) and / or carboxyl groups for reaction with self-crosslinking phenolic varnish resins, and / or combinations thereof (including copolymers thereof, such as polyether-acrylic). The second polymer is preferably not prepared using bisphenol A, bisphenol F, and bisphenol S or any reactants derived therefrom (e.g., the diglycidyl ether of bisphenol A, “BADGE”). In some embodiments, the second polymer is not prepared using any bisphenol or any reactants derived therefrom.

[0072] In some embodiments, the second polymer has a number-average molecular weight of at least 2,000 g / mol, at least 3,000 g / mol, or at least 4,000 g / mol. In some embodiments, the second polymer has a number-average molecular weight of up to 20,000 g / mol, up to 10,000 g / mol, or up to 7,000 g / mol. The number-average molecular weight can be determined by gel permeation chromatography (GPC). In other methods, the second polymer has an acid value of at least about 0 mg KOH / g resin and preferably about 0 mg KOH / g resin to about 150 mg KOH / g resin. The second polymer may also have a hydroxyl value of at least about 15 mg KOH / g resin and preferably about 20 mg KOH / g resin to about 200 mg KOH / g resin. In some embodiments, the glass transition temperature (Tg) of the second polymer described herein may be greater than 70°C, greater than 80°C, greater than 90°C, or greater than 100°C, and in some methods, less than 150°C, less than 140°C, less than 120°C, or less than 110°C.

[0073] Examples of suitable polyether second polymers for use in the coating compositions of this disclosure include those containing multiple aromatic ether segments. The polyether polymer can be formed, for example, from a reactant comprising a compound containing a polyhydroxyphenol group (more typically a compound containing a dihydroxyphenol group) and a polyepoxide, which can be an aliphatic polyepoxide or a polyepoxide of a compound containing a polyhydroxyphenol group (more typically a diepoxide of a compound containing a dihydroxyphenol group). Such polyether second polymers may contain one or more segments having one or more optionally substituted aryl or heteroaryl groups in their main chain portion. In some embodiments, one or more of these aryl or heteroaryl groups contain one or more substituent groups (preferably "bulky" substituent groups) that are preferably attached to the ring in an ortho or meta position, more preferably in an ortho position, relative to an oxygen atom attached to the ring (which is typically an oxygen atom of an ether bond or an ester bond (more typically an ether bond)). In some embodiments, one or more fragments comprise two or more aryl groups or heteroaryl groups, wherein at least two of the aryl groups or heteroaryl groups comprise an oxygen atom attached to the ring and a substituent group (preferably a "bulky" substituent group) preferably attached to the ring at an ortho or meta position relative to the oxygen atom. Non-limiting examples of such materials having ortho substituent groups include tetramethylbisphenol F (TMBPF), diepoxides of TMBPF, and polymers formed therefrom. Examples of suitable such polymers are described in U.S. Patent Publication No. 2013 / 0316109 (Niederst et al.), the entire contents of which are incorporated herein by reference.

[0074] In some embodiments, the second polymer is a polyether (e.g., an aromatic polyether). In some embodiments, the polyether second polymer has a glass transition temperature (Tg) greater than 70°C or greater than 80°C. In some embodiments, the polyether second polymer has a Tg of up to 150°C or up to 110°C. In some embodiments, the polyether second polymer is prepared by reacting a diepoxide containing an ortho-substituted bisphenol group (e.g., diglycidyl ether of tetramethylbisphenol F) with an extender (e.g., a bisphenol group-containing compound, such as hydroquinone or a diacid). Examples of suitable such polymers are described in U.S. Patent Publication No. 2013 / 0316109 (Niederst et al.). Examples of suitable polyether polymers (BPA-free) are disclosed in U.S. Patent No. 9,409,219 (Niederst et al.), U.S. Patent Publication No. 2013 / 0206756 (Niederst et al.), U.S. Patent Publication No. 2015 / 0021323 (Niederst et al.), and International Publications Nos. 2015 / 160788 (Valspar Sourcing), 2015 / 164703 (Valspar Sourcing), 2015 / 057932 (Valspar Sourcing), and 2015 / 179064 (Valspar Sourcing), each of which is incorporated herein by reference in its entirety.

[0075] Examples of commercially available polyester second polymers suitable for coating compositions of this disclosure include saturated polyesters available under the trade names DYNAPOL L, LH, and LS (Degussa AG, 45764 Marl, Germany); amorphous copolyesters available under the trade names VYLON GK330 and GK640 (Toyobo Co. Ltd., Osaka 530-8230, Japan); saturated thermoplastic polyesters available under the trade names SYNOLAC 75 NA 64 (medium molecular weight) and SYNOLAC 0691 S 60 (high molecular weight) (both available from Cray Valley, F-92091 Paris La Defense Cedex, France); and alkyd polyester resins (e.g., available under the trade names URALAC AN621 S-2 60 and URALAC AN637 S-2 60 (available from DSM Neoresins BV, 5140 AC Waalwijk, (Those available from the Netherlands) and other polyesters available under the trade names DESMOPEN T 1665 SN / IB and RUCOTE 552 (both available from Bayer Material Science AG, D-51368, Leverkusen, Germany) as well as URALAC SN800 S2G3-60, URALAC SN852 S2F-60 and URALACSN859 S2G3-50 (all available from DSM Neoresins BV, 5140 AC Waalwijk, Netherlands). Other suitable polyester second polymers are described in U.S. Patents 8,367,171, 8,574,672, 8,449,960, 9,096,772, 9,187,213, 9,650,176, and 11,827,803, and U.S. Publication No. 2020 / 0263053, which are incorporated herein by reference.

[0076] The acrylic second polymer suitable for the coating compositions of this disclosure comprises the reaction product of the composition, which includes (meth)acrylate, an olefinically unsaturated monofunctional or polyfunctional acid, and optionally a vinyl compound. For example, the acrylate second polymer may be the reaction product comprising ethyl acrylate, acrylic acid, and styrene (preferably in the presence of 2,2'-azobis(2-methyl-butyronitrile) and tert-butyl peroxybenzoate radical initiator).

[0077] Examples of suitable (meth)acrylates (i.e., methacrylates and acrylates) include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, amyl (meth)acrylate, isoamyl (meth)acrylate, hexyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, cyclohexyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, benzyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, lauryl (meth)acrylate, isobornyl (meth)acrylate, octyl (meth)acrylate, and nonyl (meth)acrylate. Examples of suitable olefinically unsaturated monofunctional or polyfunctional acids include methacrylic acid, acrylic acid, crotonic acid, itaconic acid, maleic acid, mesoconic acid, citraconic acid, sorbic acid, and fumaric acid.

[0078] Examples of suitable vinyl compounds include styrene, halostyrene, isoprene, conjugated butadiene, α-methylstyrene, vinyltoluene, vinylnaphthalene, vinyl chloride, acrylonitrile, methacrylonitrile, vinyl acetate, vinyl propionate, vinylcyclohexane, vinylcyclooctane, vinylcyclohexene, and vinyl stearate.

[0079] Examples of commercially available acrylic second polymers suitable for coating compositions of this disclosure include those available under the trade names VIACRYL SC 454 / 50BSNB, VIACRYL SC383w / 50WA, and VANCRYL 2900 DEV (all from Cytec Industries Inc., West Patterson, NJ), and NEOCRYL A-639, NEOCRYL XK-64, URACON CR203 M3, and URACON CS113 S1G (all from DSM Neoresins BV, 5140 AC Waalwijk, Netherlands). Examples of acrylic second polymers can be found in U.S. Patent No. 7,592,047 (O'Brien), U.S. Patent No. 7,189,787 (O'Brien), U.S. Patent No. 8,168,276 (Cleaver et al.), U.S. Patent No. 9,181,448 (Li et al.), U.S. Patent No. 9,394,456 (Rademacher et al.), U.S. Patent Publication No. 2016 / 0009941 (Rademacher et al.), U.S. Patent Publication No. US2016 / 0376446 (Gibanel et al.), U.S. Patent Publication No. 2017 / 0002227 (Gibanel et al.), and U.S. Patent Publication No. 2018 / Numbers 0265729 (Gibanel et al.), WO2016 / 196174 (Singer et al.), WO2016 / 196190 (Singer et al.), WO2017 / 112837 (Gibanel et al.), WO2017 / 180895 (O'Brien et al.), WO2018 / 085052 (Gibanel et al.), WO2018 / 075762 (Gibanel et al.), WO2019 / 078925 (Gibanel et al.), WO2019 / 046700 (O'Brien et al.), and WO2019 / 046750 (O'Brien et al.) are each incorporated herein by reference in their entirety.

[0080] Examples of suitable polyolefin second polymers for use in the coating compositions of this disclosure include maleic acid-modified polyethylene, maleic acid-modified polypropylene, ethylene-acrylic acid copolymer, ethylene-methacrylic acid copolymer, propylene-acrylic acid copolymer, propylene-methacrylic acid copolymer, and ethylene-vinyl alcohol copolymer.

[0081] Examples of commercially available polyolefin second polymers suitable for coating compositions of this disclosure include those obtained under the trade names DOW PRIMACOR 5980i, DUPONT NUCREL, POLYBOND 1103, NIPPON SOARNOL (EVOH), ARKEMA OREVAC 18751, and ARKEMA OREVAC 18360. Examples of polyolefin second polymers can be found in U.S. Patent No. 9,000,074 (Choudhery), U.S. Patent No. 8,791,204 (Choudhery), and International Publication No. WO 2014 / 140057 (Akzo Nobel), U.S. Patent No. 8,722,787 (Romick et al.), U.S. Patent No. 8,779,053 (Lundgard et al.), and U.S. Patent No. 8,946,329 (Wilbur et al.), each of which is incorporated herein by reference in its entirety.

[0082] For waterborne coating compositions, the preferred second polymer is a polyether-acrylic second polymer, wherein the acrylate (i.e., acrylic) portion provides water-dispersible groups. In some embodiments, the polyether-acrylic polymer is a latex polymer. Examples of such latexes are described, for example, in WO2017 / 180895 (O'Brien et al.) and International Application WO2019046700 (O'Brien et al.), each of which is incorporated herein by reference in its entirety.

[0083] Food or beverage container coating composition

[0084] In another aspect, the present invention is a food or beverage container coating composition comprising (a) a combination of a self-crosslinking phenolic varnish resin as described in any embodiment herein, (b) a second polymer discussed above, and (c) an optional water-based or solvent-based liquid carrier. The food or beverage container coating compositions of this invention preferably comprise an excess of the second polymer relative to the self-crosslinking phenolic varnish resin by weight. While non-food contact coating compositions are within the scope of the invention, preferred coating compositions are packaging coating compositions suitable for use as food contact coatings. The coating compositions may also contain catalysts (such as, for example, acid catalysts) to enhance curing and / or crosslinking. The coating compositions may also contain optional additional polymers, optional additional methyl phenolic resins and / or phenolic varnish resins, optional other hydroxyl-reactive and / or carboxyl-reactive crosslinking agents, and optional additional components. Although liquid carrier-based coating compositions are preferred, the coating compositions of the present invention are expected to be applicable in other coating application techniques (such as, for example, powder coating, extrusion coating, or lamination). The preferred cured coatings of the present invention exhibit a suitable balance of coating properties, including excellent chemical resistance, excellent manufacturability, and good adhesion.

[0085] The coating compositions disclosed herein may contain any suitable amount of self-crosslinking phenolic varnish resin to produce the desired results. In a preferred embodiment, the preferred food or beverage container coating compositions herein contain at least about 1% by weight of self-crosslinking phenolic varnish resin, in another embodiment at least about 5% by weight, in another embodiment at least about 10% by weight, in yet another embodiment at least about 15% by weight, and in yet another embodiment at least about 20% by weight of self-crosslinking phenolic varnish resin, wherein the weight percentage represents the percentage of non-volatile self-crosslinking phenolic varnish resin content by weight relative to the total non-volatile coating content by weight. Preferably, the coating compositions herein contain up to about 95% by weight of self-crosslinking phenolic varnish resin, in another embodiment up to about 75% by weight, in another embodiment up to about 50% by weight, in yet another embodiment up to about 30% by weight, and in yet another embodiment up to about 20% by weight, wherein the weight percentage also represents the percentage of non-volatile self-crosslinking phenolic varnish resin content by weight relative to the total non-volatile coating content by weight. In some embodiments, the self-crosslinking phenolic varnish resin may optionally be present in an amount of 100% by weight, and in this optional context, there is no explicit second polymer as discussed herein. In such optional embodiments, the self-crosslinking phenolic varnish resin is both a film-forming agent and a crosslinking agent (i.e., it undergoes self-crosslinking).

[0086] The coating compositions disclosed herein may contain any suitable amount of a second polymer to produce the desired results, and preferably, the composition contains an excess of the second polymer relative to the self-crosslinking phenolic varnish resin by weight. In some optional embodiments, the coating compositions herein do not contain any second polymer, and the presence of the self-crosslinking phenolic varnish resin substitutes for the second polymer. In a preferred embodiment, the food or beverage container coating compositions herein contain at least about 50% by weight of the second polymer, in another embodiment at least about 60% by weight, in yet another embodiment at least about 70% by weight, in still another embodiment at least about 75% by weight, and in yet another embodiment at least about 80% by weight, wherein the weight% represents the percentage of the weight of the non-volatile second polymer content (which may optionally contain two or more different second polymers) to the total non-volatile coating content. Preferably, the coating composition of the present invention comprises up to about 99% by weight of a second polymer, up to about 95% by weight of a second polymer, up to about 90% by weight of a second polymer, up to about 85% by weight in another embodiment, up to about 70% by weight in another embodiment, up to about 65% by weight in yet another embodiment, and up to about 60% by weight in yet another embodiment, wherein the weight percentage also represents the percentage of the weight of the non-volatile second polymer content to the total weight of the non-volatile coating content. In a particular embodiment, the food or beverage container coating composition comprises about 5% by weight to about 50% by weight of a self-crosslinking phenolic varnish resin (preferably about 20% by weight to about 40% by weight of a self-crosslinking phenolic varnish resin) and about 50% by weight to about 95% by weight of a second resin (preferably about 80% by weight to about 60% by weight of a second resin) based on total resin solids.

[0087] The preferred coating compositions of the present invention preferably contain less than 10,000 ppm, more preferably less than 1,000 ppm, even more preferably less than about 500 ppm, or most preferably less than 100 ppm, or in alternative embodiments, more preferably substantially free, more preferably substantially free, even more preferably substantially completely free, and best completely free of each or at least one of formaldehyde or phenol. In some preferred embodiments, the coating compositions of this disclosure are preferably substantially free, more preferably substantially free, even more preferably substantially completely free, and best completely free of BPA, BPF, BPS, and epoxides of BPA, BPS, and BPF. The formaldehyde content described herein is determined according to the procedure of EN ISO 9397.

[0088] When present, the concentration of one or more optional additional crosslinking agents may vary depending on the desired results. For example, in some embodiments, the coating composition may contain about 0.01% to about 40% by weight, more preferably about 0.5% to about 35% by weight, or even more preferably about 3% to about 30% by weight of the non-volatile material in the coating composition, based on the weight of the non-volatile material in the coating composition.

[0089] Any suitable, optional additional crosslinking agent may be used. For example, amino crosslinking agents (e.g., amino plastics), end-capped isocyanate crosslinking agents, β-hydroxyalkylamide crosslinking agents, carbodiimide crosslinking agents, materials containing ethylene oxide groups (e.g., ethylene oxide-functionalized polyesters, such as glycidyl-modified polyesters or ethylene oxide-functionalized vinyl polymers (such as acrylic resins formed using glycidyl methacrylate)), and combinations thereof may be used.

[0090] The coating composition may optionally include an amino-crosslinking resin (e.g., an amino plastic). The amino-crosslinking resin is typically a condensation product of an aldehyde (e.g., formaldehyde, acetaldehyde, crotonaldehyde, and benzaldehyde) with a substance containing an amino group or an amide group (e.g., urea, melamine, and benzoguanamine). Suitable amino-crosslinking resins include, for example, benzoguanamine-formaldehyde resins, melamine-formaldehyde resins (e.g., hexamethoxymethylmelamine), etherified melamine-formaldehyde, urea-formaldehyde resins, and mixtures thereof.

[0091] Condensation products of other amines and amides can also be used, such as triazines, diazines, triazoles, guanidines, guanidineamines, and aldehyde condensates of alkyl-substituted and aryl-substituted melamines. Some examples of such compounds are N,N'-dimethylurea, benzourea, dicyandiamide, formylguanidine, acetylguanidine, glycourea, cyanuric acid monoamide 2-chloro-4,6-diamino-1,3,5-triazine, 6-methyl-2,4-diamino-1,3,5-triazine, 3,5-diaminotriazole, triaminopyrimidine, 2-mercapto-4,6-diaminopyrimidine, 3,4,6-tris(ethylamino)-1,3,5-triazine, etc. Although the aldehyde used is usually formaldehyde, other similar condensation products can be prepared from other aldehydes, such as acetaldehyde, crotonaldehyde, acrolein, benzaldehyde, furfural, glyoxal, etc., and mixtures thereof.

[0092] Suitable commercially available amino crosslinking resins include, for example, CYMEL 301, CYMEL 303, CYMEL 370, CYMEL 373, CYMEL 1131, CYMEL 1125, as well as CYMEL 5010 Maprenal MF 980 (all available from CytecIndustries Inc., West Patterson, NJ) and Uramex BF 892 (available from DSM, Netherlands).

[0093] Non-limiting examples of end-capped isocyanate crosslinking agents include aliphatic and / or alicyclic end-capped polyisocyanates, such as HDI (hexamethylene diisocyanate), IPDI (isophorone diisocyanate), TMXDI (bis[4-isocyanocyclohexyl]methane), H 12 MDI (tetramethylene-m-dimethylisocyanate), TMI (isopropenyl dimethyl-benzyl isocyanate), and their dimers or trimers. Suitable capping agents include, for example, n-butyl ketone oxime, ε-caprolactam, diethyl malonate, and secondary amines. Non-limiting examples of suitable commercially available capped isocyanate crosslinking agents include VESTANAT B 1358 A, VESTANAT EP B 1186 A, VESTANA EP B 1299 SV (all available from Degussa Corp., Marl, Germany); and DESMODUR VPLS 2078 and DESMODURBL 3175 (available from Bayer AG, Leverkusen, Germany). In some embodiments, capped isocyanates with Mn of at least about 300, more preferably at least about 650, and even more preferably at least about 1,000 can be used.

[0094] A preferred optional component is a catalyst that increases the curing rate and / or the degree of crosslinking. This catalyst is typically selected from those known for crosslinking and / or electrophilic substitution of aromatic rings in methyl phenolic resins. Examples of such catalysts include, but are not limited to, strong acids (e.g., dodecylbenzenesulfonic acid (DDBSA, available from Cytec as CYCAT 600), methanesulfonic acid (MSA), p-toluenesulfonic acid (pTSA), dinonylnaphthalenedisulfonic acid (DNNDSA), sulfuric acid, trifluoromethanesulfonic acid, phosphoric acid, and mixtures thereof, and bases (e.g., dimethylethanolamine, 1,5-diazabicyclo(4,3,0)non-5-ene (“DBN”), 1,5-diazabicyclo(4,3,0)non-7-ene (“DBU”), and NaOH).

[0095] The coating compositions disclosed herein are currently preferred for food or beverage coating applications, and particularly for food contact coatings. While not intended to be bound by any theory, cured packaging coatings formulated using the self-crosslinking phenolic varnish resin of this disclosure (with or without optional additional polymers, other components, or crosslinking agents, such as, for example, amino plastics and / or terminal isocyanates) have been observed to exhibit superior coating properties (e.g., excellent chemical resistance) compared to comparable coating compositions formulated with other types of crosslinking agents (e.g., amino and / or terminal isocyanates alone, without vinyl methyl phenolic crosslinking agents) or conventional polymer / methyl phenolic resin crosslinking agent systems. In a preferred embodiment, it is also believed that during the curing (e.g., thermosetting) of the coating composition, the self-crosslinking phenolic varnish resin forms covalent bonds with the hydroxyl groups of the second polymer to form a cured coating, thereby forming a crosslinked polymer network comprising the self-crosslinking phenolic varnish resin and the second polymer.

[0096] If used, the catalyst is preferably present in an amount of at least 0.01% by weight, and more preferably at least 0.1% by weight, based on the weight of the non-volatile material. If used, the catalyst is preferably present in an amount of no more than 3% by weight, and more preferably no more than 1% by weight, based on the weight of the non-volatile material.

[0097] If desired, the coating compositions of this disclosure may optionally contain other additives that will not adversely affect the coating composition or the cured coating produced therefrom. Suitable additives include, for example, those that improve the processability or manufacturability of the composition, enhance the aesthetics of the composition, or improve specific functional properties or characteristics (such as adhesion to a substrate) of the coating composition or the cured composition produced therefrom. Additives that may be included are carriers, additional polymers, emulsifiers, pigments, metal powders or pastes, fillers, anti-migration agents, antimicrobial agents, extenders, curing agents, lubricants, coalescing agents, wetting agents, biocides, plasticizers, crosslinking agents, defoamers, colorants, waxes, antioxidants, preservatives, flow control agents, thixotropic agents, dispersants, adhesion promoters, UV stabilizers, scavengers, or combinations thereof. The amount of each optional component that may be included is sufficient for its intended purpose, but preferably such amounts will not adversely affect the coating composition or the cured coating produced therefrom.

[0098] Any suitable carrier can be used to prepare the coating compositions of the present invention. Suitable carriers include carrier liquids, such as organic solvents, water, and mixtures thereof. Suitable organic solvents include aliphatic hydrocarbons (e.g., mineral oil, kerosene, high flash point VM&P naphtha, etc.); aromatic hydrocarbons (e.g., benzene, toluene, xylene, solvent naphtha 100, 150, 200, etc.); alcohols (e.g., ethanol, n-propanol, isopropanol, n-butanol, isobutanol, etc.); ketones (e.g., acetone, 2-butanone, cyclohexanone, methyl aryl ketone, ethyl aryl ketone, methyl isopentyl ketone, etc.); esters (e.g., ethyl acetate, butyl acetate, etc.); glycols (e.g., butyl ethylene glycol); glycol ethers (e.g., ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, propylene glycol monomethyl ether, etc.); glycol esters (e.g., butyl ethylene glycol acetate, methoxypropyl acetate, etc.); cyclic or acyclic ethers (e.g., mixtures of ether isomers (e.g., CAS No. 111109-77-4), THF, di(propylene glycol) dimethyl ether, etc.); and mixtures thereof. Preferably, a liquid carrier is selected to provide a dispersion or solution of the self-crosslinking phenolic varnish resin of this disclosure for further formulation.

[0099] In some embodiments, the coating compositions described herein may be water-based varnishes. In some such embodiments, preferably, the coating composition contains at least about 50% by weight of total volatiles, more preferably at least about 60% by weight of total volatiles, and even more preferably at least about 75% by weight of total volatiles. Certain coating compositions of the present invention contain at least about 10% by weight of total volatiles based on the total weight of the coating composition, more preferably at least about 20% by weight of total volatiles, and even more preferably at least about 40% by weight of total volatiles (about 50% by weight or more in some embodiments).

[0100] The food or beverage container coating compositions disclosed herein can be prepared in various ways using conventional methods. For example, the coating composition can be prepared by simply mixing a self-crosslinking phenolic varnish resin and a second polymer, along with any other optional ingredients, in any desired order under adequate stirring. The resulting mixture can be mixed until all compositional components are substantially homogeneously blended. Alternatively, the coating composition can be prepared as a liquid solution or dispersion by mixing an optional carrier liquid, a self-crosslinking phenolic varnish resin or a self-crosslinking phenolic varnish resin and a second polymer, along with any other optional ingredients, in any desired order under adequate stirring. Additional amounts of carrier liquid can be added to the coating composition to adjust the amount of non-volatile materials in the coating composition to a desired level.

[0101] The total amount of solids present in the coating compositions described herein can vary depending on various factors, including, for example, the desired application method. Currently preferred coating compositions contain at least about 18% by weight, at least about 19% by weight, more preferably at least about 20% by weight, more preferably at least about 30% by weight, more preferably at least about 35% by weight, and even more preferably at least about 40% by weight of solids based on the total weight of the coating composition. Preferably, the coating composition contains less than about 80% by weight, more preferably less than about 70% by weight, and even more preferably less than about 65% by weight of solids based on the total weight of the coating composition.

[0102] In another embodiment, this disclosure provides a coating composition comprising a combination of a self-crosslinking phenolic varnish resin and an optional thermoplastic dispersion, as well as optional other components. Such coating compositions are suitable for a variety of applications, such as, for example, food or beverage packaging applications. While not intended to be bound by any theory, it is believed that certain combinations of self-crosslinking phenolic varnish resin and second polymer herein can stabilize certain thermoplastic materials, such as, for example, polyvinyl chloride (“PVC”), to prevent or reduce degradation of the thermoplastic material or cured coatings thereof. Therefore, in an optional embodiment, an effective amount of self-crosslinking phenolic varnish resin and second polymer is used in the organosol or plasticizer coating composition (e.g., for the purpose of stabilizing the thermoplastic dispersion). Organosols that can be used in the compositions herein include, for example, vinyl organosols. As used herein, a “vinyl organosol” comprises dispersed polymer particles of a vinyl chloride polymer (preferably a high molecular weight vinyl chloride polymer) in a liquid carrier. Discussions of suitable materials and methods of preparation for such compositions can be found, for example, in PCT / US2008 / 058899.

[0103] The organosol coating compositions described herein preferably comprise at least about 10% by weight, more preferably at least about 15% by weight, and even more preferably at least about 20% by weight, of a second polymer based on the total non-volatile weight of the coating composition. The organosol coating compositions preferably comprise less than about 90% by weight, more preferably less than about 70% by weight, and even more preferably less than about 60% by weight, of a second polymer based on the total non-volatile weight of the coating composition.

[0104] The organosol coating composition of the present invention preferably comprises at least about 10% by weight, more preferably at least about 15% by weight, and even more preferably at least about 20% by weight of thermoplastic material based on the total non-volatile weight of the coating composition. The organosol coating composition preferably comprises less than about 80% by weight, more preferably less than about 70% by weight, and even more preferably less than about 65% by weight of thermoplastic material based on the total non-volatile weight of the coating composition.

[0105] The concentration of the self-crosslinking phenolic varnish resin in the organosol coating composition of the present invention can be varied according to the desired results. For example, in some embodiments, the organosol coating composition comprises a self-crosslinking phenolic varnish resin, preferably at least about 0.5% by weight, more preferably at least about 1% by weight, and even more preferably at least about 4.5% by weight, based on the weight of the non-volatile materials in the coating composition. The amount of self-crosslinking phenolic varnish resin contained in the coating composition, preferably less than about 15% by weight, more preferably less than about 7% by weight, and even more preferably less than about 5% by weight, based on the weight of the non-volatile materials in the coating composition.

[0106] Examples of suitable thermoplastic materials include halogenated polyolefins, such as vinyl chloride, vinylidene fluoride, polychloroprene, polychloroisoprene, polychlorobutylene, and copolymers and homopolymers of combinations thereof. PVC is a particularly preferred thermoplastic material. The number-average molecular weight (Mn) of the thermoplastic material is preferably from about 40,000 g / mol to about 300,000 g / mol; more preferably from about 75,000 g / mol to about 200,000 g / mol; and even more preferably from about 100,000 g / mol to about 150,000 g / mol.

[0107] In applications involving packaging coatings, dispersed thermoplastic particles are preferred, wherein the particle size ranges from greater than 0 micrometers to about 5 micrometers based on the volume average median particle diameter. However, other sizes may be used, such as non-dispersed thermoplastic particles ranging from about 5 micrometers to about 100 micrometers based on the volume average median particle diameter.

[0108] Thermoplastic materials are preferably dispersed in a liquid carrier to form a thermoplastic dispersion. Examples of suitable liquid carriers include organic solvents, plasticizers, or mixtures thereof. Suitable organic solvents may include polar solvents such as ketones (e.g., MIBK and DIBK), glycol ethers, alcohols, aliphatic hydrocarbons, aromatic hydrocarbons, or mixtures thereof. In some embodiments, it may be advantageous to select solvents that have an affinity for the thermoplastic material and / or solvents that can cause the thermoplastic particles to swell to promote the storage stability of the liquid coating composition. Preferred liquid carriers exhibit sufficient volatility to substantially evaporate from the coating composition during the curing process.

[0109] The cured coating of the present invention preferably adheres well to metals (e.g., steel, tin-free steel (TFS), tinplate, electrolytic tinplate (ETP), aluminum, etc.) and provides a high level of resistance to corrosion or degradation that may result from prolonged exposure to products such as food or beverage products. The coating can be applied to any suitable surface, including the inner surface of a container, the outer surface of a container, the ends of a container, and combinations thereof.

[0110] The coating composition of the present invention can be applied to a substrate using any suitable procedure, such as spraying, roller coating, roll coating, curtain coating, dip coating, meniscus coating, coincidence coating, scraper coating, knife coating, dip coating, slot coating, slope coating, and other types of predetermined amount coating. In one embodiment, when the coating is used to coat metal sheets or rolls, the coating can be applied by roller coating.

[0111] The coating composition may be applied to the substrate before or after it is formed into an article. In some embodiments, at least a portion of a planar substrate is coated with one or more layers of the coating composition of the present invention, and then cured before the substrate is formed into an article.

[0112] In some embodiments, the food or beverage container coating compositions of this disclosure are heat-curable at a temperature of at least 176°C or at least 190°C. In some embodiments, the food or beverage container coating compositions of this disclosure are heat-curable at a temperature of up to 250°C or up to 235°C.

[0113] In some embodiments, the food or beverage container coating composition of this disclosure is heat-curable within a timeframe of at least 10 seconds, at least 20 seconds, or at least 30 seconds. In some embodiments, the food or beverage container coating composition of this disclosure is heat-curable within a timeframe of at most 30 minutes, at most 20 minutes, at most 10 minutes, or at most 5 minutes.

[0114] After the coating composition is applied to a substrate, various processes can be used to cure the composition, including, for example, oven baking by conventional or convection methods. The curing process can be carried out in discrete or combined steps. For example, the coated substrate can be dried at ambient temperature to keep the coating composition in a largely uncrosslinked state. The coated substrate can then be heated to fully cure the coating composition. In some cases, the coating composition can be dried and cured in a single step. In a preferred embodiment, the coating composition of the present invention is a thermosetting coating composition.

[0115] The curing process can be carried out at any suitable temperature, including, for example, temperatures in the range of about 180°C to about 250°C. If the metal coil is the substrate to be coated, the curing of the applied coating composition can be carried out, for example, by subjecting the coated metal to a temperature of about 230°C to about 250°C for about 15 to 30 seconds. If the metal sheet is the substrate to be coated (e.g., for manufacturing three-piece food cans), the curing of the applied coating composition can be carried out, for example, by subjecting the coated metal to a temperature of about 190°C to about 210°C, in some embodiments for only a few seconds (at most 30 seconds or 10 to 20 seconds), or in other embodiments for about 3 minutes to about 50 minutes (or about 3 minutes to about 30 minutes).

[0116] The coating compositions disclosed herein preferably have a viscosity (ASTM D2983) suitable for a given coating application. While various application methods are possible, the coating compositions may have a viscosity suitable for spraying. In other embodiments, the coating composition has a viscosity of at least about 25 centipoise (cps) (25 mPas), in other embodiments at least about 50 mPas, in other embodiments at least about 150 mPas, in other embodiments at least about 500 mPas, and in still other embodiments at least about 750 mPas. In other embodiments, the coating composition has a viscosity of up to about 5000 mPas, in other embodiments up to about 4000 mPas, in other embodiments up to about 3000 mPas, and in still other embodiments up to about 2000 mPas.

[0117] The coating compositions disclosed herein are heat-curable. In this document, "heat-curable" refers to the temperature and time conditions typically used in container coating production lines. For this purpose, specific temperature and time ranges are oven temperatures or "PMT" (peak metal temperature).

[0118] The coating compositions of the present invention can be used in a variety of coating applications. The coating compositions are particularly suitable as adhesive coatings for the inner or outer surfaces of metal containers. Examples of such articles include closures (including, for example, the inner surface of a twist-top lid for food and beverage containers); inner crowns; two-piece and three-piece cans (including, for example, food and beverage containers); shallow-drawn cans; deep-drawn cans (including, for example, multi-stage drawn and redrawn food cans); can ends (including, for example, easy-open can ends); monomeric aerosol containers; and general industrial containers, cans, and can ends.

[0119] The food or beverage container coating compositions described herein are applicable to the inner or outer surfaces of metal food or beverage containers, including food contact surfaces. In embodiments, the cured coating is retortable when used in food and beverage container applications. In embodiments, the cured coatings of the compositions described herein are capable of withstanding the high-temperature conditions typically associated with cooking processes or other food or beverage preservation or sterilization processes. Particularly preferred cured coatings exhibit enhanced resistance to such conditions when in contact with food or beverage products that exhibit one or more corrosive (or aggressive) chemical properties under such conditions. Examples of such corrosive food or beverage products may include meat-based products, dairy-based products, fruit-based products, energy drinks, and acidic or acidified products.

[0120] In another embodiment, the food or beverage container coating compositions described herein are suitable for the surfaces of containers for household products, such as paint cans, aerosol containers, steel containers, and other containers.

[0121] In some embodiments, the food or beverage container coating compositions described herein are suitable for use as coatings on food contact surfaces of the sidewalls of three-piece food cans. The coating compositions are typically applied to a sheet of metal, which is then typically cured before the coated sheet is manufactured into the sidewalls of a three-piece food can.

[0122] In some embodiments, the food or beverage container coating compositions described herein are storage stable. As contemplated herein, a “storage stable” coating composition means that, when all components of the coating composition are mixed and stored before application to a substrate, the coating composition will retain its ability to be applied to the substrate during storage (at least a certain amount of storage time) and then cure after application. In a preferred embodiment, the coating composition is storage stable at ambient temperature for at least 20 days, in another embodiment for at least one month, in yet another embodiment for at least three months, and in still another embodiment for at least six months.

[0123] The uses of the food or beverage container coating compositions described herein include: providing a coating composition as described herein; applying the coating composition to at least a portion of a metal substrate before or after forming a metal substrate into a food or beverage container (e.g., a can) or a portion thereof; and thermosetting the coating composition.

[0124] In some embodiments of such methods, the metal substrate includes a steel substrate or an aluminum substrate. In some embodiments of such methods, the coating composition is applied to a pre-formed food or beverage container, or a portion thereof. That is, in some embodiments, the metal substrate is in the form of a pre-formed food or beverage container having sidewalls and a bottom, and the coating includes coating the inner surfaces of the sidewalls and the bottom.

[0125] In some embodiments of such methods, a coating composition is applied to a food or beverage contact surface of a metal substrate (e.g., the inside of a food or beverage container or a surface that will become the inside of a food or beverage container). Therefore, the methods disclosed herein may involve applying a coating composition to a flat substrate and then forming the flat metal substrate as at least a portion of a food or beverage container after thermosetting the coating composition.

[0126] In some embodiments of such methods, applying the coating composition comprises sufficient to form a coating with a concentration of 1 mg / in 2 (i.e., 1.55g / m) 2 Up to 20 mg / in 2 (i.e., 31g / m) 2 The amount of cured coating, equal to the average dry film weight, is applied to the metal substrate by applying the coating composition.

[0127] The food or beverage container coating compositions disclosed herein can be applied to a substrate before or after forming an article (such as, for example, a food or beverage container or a portion thereof). In one embodiment, a method of forming a food or beverage container is provided, comprising: applying the coating composition described herein (via spraying, dipping, etc.) to a metal substrate (e.g., applying the composition to a metal substrate in the form of a flat roll or sheet), thermosetting the coating composition, and forming the substrate (e.g., via stamping) into a packaging container or a portion thereof (e.g., a food or beverage container or a portion thereof). For example, two-piece or three-piece cans or portions thereof, such as riveted beverage can ends (e.g., soft drink cans or beer cans), having a cured coating of the disclosed coating composition on the surface of the can can be formed by such a method.

[0128] In other embodiments, this disclosure also provides methods including using any embodiment of the food or beverage coating composition described herein on a metal substrate (or a portion thereof) of a metal food or beverage container or packaging. In some cases involving multiple parties, a first party (e.g., a party manufacturing and / or supplying the food or beverage container coating composition) may provide a second party (e.g., a metal coating machine (e.g., a sheet coating machine for a food body or the end of a food can), a can manufacturer, or a brand owner) with instructions, suggestions, or other disclosures regarding the end use of the food or beverage container coating composition. Such disclosures may include, for example, instructions, suggestions, or other disclosures relating to coating a metal substrate for subsequent use in forming a packaging container or a portion thereof, coating a metal substrate of a pre-formed container or a portion thereof, preparing a coating composition for such use, curing conditions or process-related conditions for such coatings, or instructions, suggestions, or other disclosures relating to a suitable type of packaging product for the resulting coating. Such disclosures may appear, for example, in technical data sheets (TDS), safety data sheets (SDS), regulatory disclosures, warranties or limitations of warranties, marketing materials or presentations, or on a company website. A first party that makes such disclosure to a second party shall be deemed to have “made” any embodiment of the coating composition herein used on a metal substrate of metal packaging (e.g., a container or closure), even if it is a second party that commercially applies the composition to a metal substrate, uses a commercially available substrate with such coating on a metal substrate of a packaging container, and / or fills such coated containers with the product.

[0129] Test methods

[0130] Unless otherwise specified, the following test methods are used in the following embodiments.

[0131] Solvent resistance test ("MEK dual friction")

[0132] The degree of “curing” or crosslinking of a coating is measured as its resistance to solvents such as methyl ethyl ketone (MEK). This test is performed as described in ASTM D 5402-93. The number of bi-friction cycles (i.e., one round trip) up to failure is reported. Preferably, the MEK solvent resistance is at least 30 bi-friction cycles (DR). Generally, high MEK friction indicates a high crosslinking density, which typically corresponds to good solvent resistance (e.g., chemicals). For example, coating films used in food cans should be highly crosslinked (at least 30 bi-friction cycles, typically at least 50 bi-friction cycles) because many food substances can cause corrosion.

[0133] Adhesion test

[0134] Adhesion testing is performed according to ASTM D3359-17 using a Scotch 610 model available from 3M (Saint Paul, MN). Adhesion is typically rated on a scale of 0B to 5B, where the rating is based on the percentage of the initially coated area of ​​the sample that shows evidence of paint peeling and / or paint removal. Scores of 5B, 4B, 3B, 2B, 1B, and 0B indicate, respectively, that 0%, less than 5%, 5% to 15%, 15% to 35%, 35% to 65%, and greater than 65% of the initially coated area after the test show evidence of paint peeling and / or paint removal. Preferably, an adhesion score of at least 4B (i.e., 4B or 5B) is considered adhesive.

[0135] Anti-whitening test

[0136] Anti-whitening measures a coating's ability to resist erosion by various solutions. Whitening is typically measured by the amount of water absorbed into the coated film. When a film absorbs water, it usually becomes cloudy or appears white. Whitening is visually measured using a scale of 0 to 5, where a score of "0" indicates no whitening, a score of "1" indicates slight whitening, and a score of "3" indicates whitening, and so on. A whitening score of "2" or lower is generally desirable for commercial packaging coatings, and "1" or lower is optimal.

[0137] Acid value (AN) of the resin

[0138] The acid value (AN) of the resin can be measured by dissolving an appropriate amount of resin in a solution of dimethylformamide (DMF) and methyl ethyl ketone (MEK), and then titrating with 0.1 N methanol KOH and cresol red / thymol blue or phenolphthalein indicator. Based on the amount of KOH consumed, the acid value is calculated and reported as mg KOH / 1 gram of dry resin.

[0139] Hydroxyl value of resin

[0140] The hydroxyl value (HN) of the resin can be measured by dissolving an appropriate amount of resin in methylene chloride, then mixing the sample with a solution of 4-(dimethylamino)pyridine (DMAP) catalyst and 97% acetic anhydride solution in anhydrous dimethylformamide (DMF) for 15 to 20 minutes. A solution of DMF and deionized water is then added, and the solution is mixed for an additional 15 to 20 minutes. After the addition of tetrahydrofuran (THF), the hydroxyl value of the resin is measured using a titration method with 0.5 N methanol KOH and phenolphthalein indicator. The hydroxyl value is calculated based on the amount of KOH consumed compared to a titration without resin solution and reported as mg KOH / 1 g dry resin.

[0141] Viscosity (η)

[0142] This document describes the measurement of viscosity stability and / or apparent viscosity using a Brinell viscometer. The apparent viscosity of any non-Newtonian material can be determined using ASTM D2196-20. A suitable Brinell viscometer is model DV2T or equivalent (Brookfield Engineering Laboratories, Middleboro, MA). Apparent viscosity can be determined using Test Method A of ASTM D2196-20. Viscosity stability, or stable viscosity, refers to an increase in viscosity of the composition of no more than 100% relative to the viscosity of the same composition at time T0, and preferably, the viscosity change is an increase in viscosity of about 0% to less than 50% relative to the viscosity at time T0. Viscosity stability can also be measured at room temperature using a Brinell viscometer, with the rotor size and rpm selected according to the parameters of ASTM D2983.

[0143] Reverse impact test

[0144] The reverse impact test measures the ability of a coated substrate to withstand the deformation encountered when impacted with a hemispherical head onto steel. This test is performed as described in ASTM D2794-93. In short, a 1-pound (0.45 kg) standard metal bar in a cylinder is dropped from a height of 36 inches (91.4 cm) onto the substrate (using a BYK Gardner OVERBALL Bend and impact testing instrument). After the test, the coating is visually inspected for microcracks or microfractures—often referred to as cracks. The test specimen is impacted on an uncoated or reverse side. Cracks in the coating are identified through visual evaluation. The film is examined for any signs of microcracks or fissures, paying particular attention to stress / forming areas. If cracks or fissures are observed, the sample is unacceptable. If no cracks or fissures are observed, the sample is acceptable.

[0145] Differential scanning calorimetry for glass transition temperature (Tg)

[0146] Samples for differential scanning calorimetry (“DSC”) testing were first prepared by applying a liquid resin composition to an aluminum sheet panel. The panel was then baked in a Fisher Isotemp furnace at 300℉ (149°C) for 20 minutes to remove volatile substances. After cooling to room temperature, the sample was scraped off the panel, weighed into a standard sample pan, and analyzed using the standard DSC thermal calorimetry method. The sample was equilibrated at -60°C, then heated to 200°C at 20°C / min, cooled to -60°C, and then heated again to 200°C at 20°C / min. The glass transition temperature was calculated from the thermogram of the last thermal cycle. The glass transition was measured at the inflection point of the transition.

[0147] Molecular weight determined by gel permeation chromatography

[0148] Samples for gel permeation chromatography (“GPC”) testing were prepared by first dissolving liquid resin in THF. Aliquots of this solution were then analyzed using GPC along with a mixture of polystyrene (“PS”) standards and an epoxy control (Epon 1009F, supplied by Hexion, Inc.). The molecular weight of the samples was calculated after processing the GPC run and validating the PS and Epon 1009F standards.

[0149] DMA analysis

[0150] According to ASTM D4473-08 (re-approved in 2021), the dynamic mechanical properties and / or curing behavior of any samples described herein are evaluated using instruments such as the ARES G-2 rheometer (TA instruments) and rectangular torsion fixtures (TA instruments), with improved temperature ramps and / or isothermal holding as described herein.

[0151] The sample preparation used for each evaluation was identical and included a 1-inch glass fiber support strip and two 1 / 2-inch aluminum foil strips. An 8"×8" aluminum foil was placed in a fume hood as a workstation, and the glass fiber strip was placed on top of the foil. Using a disposable pipette, the thermosetting material to be evaluated was fully coated onto the top side of the fabric, then flipped over and coated onto the opposite side. Using tweezers, the coated fabric was dragged along a clean area of ​​the foil to remove excess coating from both sides and ensure the material was evenly distributed on the fabric. The aluminum foil strips were folded to cover each end of the coated fabric strip, preventing the material from curing on the grips of the torsion clamp. The sample was brought to the ARES-G2, and the aluminum-covered ends were inserted into the rectangular torsion clamp and tightened by hand with an Allen wrench. A tension of 0.5 N was manually applied to the sample using the instrument controller, and the instrument oven was closed around the sample. Next, a temperature ramp test was performed to characterize the reaction initiation temperature by identifying a sharp increase in the storage modulus at a constant temperature ramp rate. The sample was equilibrated at 50°C for 30 seconds, and then the instrument began to heat to 300°C at a constant rate of 5.0°C / min. Throughout the test, the instrument maintained a tension of 0.5 N and performed strain-controlled torsional DMA measurements at 0.1% strain, 1 Hz, and 2 points per second. The obtained data can be plotted as storage modulus [MPa] versus temperature [°C] in the TA-licensed data analysis software TRIOS [5].

[0152] If needed, TRIOS's "Start Point" tool can be used to identify the reaction initiation temperature within a temperature range where a sharp increase in storage modulus is observed after a measured period of constant storage modulus. When the thermosetting material begins to cure on the supporting woven fabric at the reaction initiation temperature, the storage modulus of the sample increases significantly as new bonds form and the polymer network becomes more rigid and structured.

[0153] The isothermal holding test aims to characterize the reaction time constant “c” based on the exponential fit of the storage modulus versus time curve when the sample is subjected to the target curing conditions. After the sample is loaded into the instrument, the oven is rapidly increased to a curing temperature of approximately 204.4 °C (400 °F) at the fastest possible speed (approximately 9.25 °C / s), and then held isothermally for 15 minutes while strain-controlled torsional DMA measurements are performed under test conditions of 0.1% strain, 1 Hz, and sampling at 2 points per second throughout the test. If desired, the relationship between storage modulus and time can be analyzed using the exponential fitting tool in TRIOS [5] to fit the storage modulus to an exponential equation as it increases over time and to determine the fitting parameters a, b, and c as shown in Equation 1.

[0154] (Equation 1)

[0155] Where y is the storage modulus, a and b are fitting parameters describing the modeled solidification storage modulus value, x is time, and c is the time constant. When time equals the time constant, Equation 1 approximately represents the storage modulus of the sample at 63% solidification, as shown in Equation 2 below.

[0156]

[0157]

[0158]

[0159] (Equation 2)

[0160] Therefore, the time constant c is equal to the time it takes for the sample to reach 63% cure. Given a set of samples tested under the DMA and oven conditions described herein, the time constants can be compared to gain insight into which sample cures fastest and slowest in terms of the time required to reach 63% cure.

[0161] Example

[0162] This disclosure is illustrated by the following examples. It should be understood that the specific embodiments, materials, quantities, and procedures are to be interpreted broadly within the scope and spirit of the invention as described herein. Unless otherwise stated in these examples and throughout this disclosure, all parts, percentages, and ratios are by weight, and all molecular weights are number average molecular weights. Unless otherwise specified, all chemicals used are commercially available, for example, from Sigma-Aldrich, St. Louis, Missouri.

[0163] Example 1

[0164] The standard resin solution was prepared as follows: 150 g of n-butanol and 90 g of Alnovol PN320 (a phenolic varnish from Allnex) were added to a 1-liter four-necked round-bottom flask equipped with a mechanical stirrer, a reflux condenser, and a thermocouple connected to the heating control and heating device. The resin was dissolved at approximately 65°C for about 30 minutes, yielding a clear orange solution. Other resin solutions shown in Table 1 were prepared using a similar process.

[0165] Table 1

[0166]

[0167] Example 2

[0168] Dibutoxymethane was prepared as follows: n-Butanol (142.1 g), paraformaldehyde (96%, 17.6 g), and sulfuric acid (98%, 0.22 g) were added to a one-liter four-necked round-bottom flask equipped with a mechanical stirrer, nitrogen inlet, reflux condenser, Dean-Stack receiver, and thermocouples connected to the heating control and heating devices. The mixture in the flask was heated to approximately 85°C. The reaction was maintained at approximately 85°C for approximately 4 hours, and the distillate (60.4 g) was collected in the Dean-Stack receiver until the formaldehyde content was below approximately 0.01%. Next, additional n-butanol (55.1 g) was added to the flask to balance the weight. The resulting product was a clear solution.

[0169] To determine the formaldehyde content of this embodiment (and any embodiments of this disclosure), the reaction for formaldehyde content was monitored using the procedure of EN ISO 9397, as follows: A given weight of the sample, weighed using an analytical balance, was dissolved in 100 mL of methanol. The pH of the solution was adjusted to 3.5 using dilute hydrochloric acid or KOH solution. Then, 15 mL of a 10% hydroxylamine hydrochloride aqueous solution (pH 3.5) was added to the solution. After mixing for 10 minutes, the solution was titrated with 0.1N standard potassium hydroxide on a Metrohm 751 GDP Titrino (±0.01 mL) until the pH reached 3.50. The formaldehyde percentage was calculated based on the following equation: Formaldehyde % = (3.0 × 0.1V (mL)) / (Sample Amount (g))

[0170] Example 3

[0171] Conventional phenolic varnish resin was functionalized as follows: 212.1 g of n-butanol and 85.0 g of phenolic varnish resin (Alnovol PN320, Allnex) were added to a one-liter four-necked round-bottom flask equipped with a mechanical stirrer, nitrogen inlet, reflux condenser, Dean-Stark receiver, and thermocouples connected to the heating control and heating devices. The phenolic varnish resin was dissolved in n-butanol at 65°C to form a clear yellow solution. Paraformaldehyde (96%, 17.6 g) and sulfuric acid (98%, 0.22 g) were added to the flask. The reaction mixture was heated and maintained at 85°C for approximately 6 hours until the solubility of the sample in the test solution was less than 1% by weight. The reaction was maintained at 85°C for another hour, and then terminated by cooling to 40°C. The distillate (66.7 g) was collected. The product was a clear, deep orange liquid. The viscosity is approximately 617 cps, the solids content is approximately 43.3%, and the free formaldehyde content is less than 0.01%. The reaction endpoint is determined when the solubility of the reaction sample in the test solution is less than 1% by weight, or when a mixture containing less than 1% of the sample becomes cloudy. The test solution is prepared by mixing methanol (100 ml) with a 10% aqueous solution of hydroxylamine hydrochloride (15 ml).

[0172] Example 4

[0173] Another conventional phenolic varnish resin was functionalized as follows: n-Butanol (141.1 g) and phenolic varnish resin (Alnovol PN320, Allnex) (85.0 g) were added to a one-liter four-necked round-bottom flask equipped with a mechanical stirrer, nitrogen inlet, reflux condenser, and thermocouples connected to the heating control and heating devices. The phenolic varnish resin was dissolved in n-butanol at 65°C to form a clear yellow solution. Paraformaldehyde (96%, 17.5 g) and sulfuric acid (98%, 0.22 g) were added to the flask. The reaction mixture was heated and maintained at 85°C for approximately 5 hours until the solubility of the sample in the test solution was less than 1% by weight. The reaction was maintained at 85°C for another 2 hours. The reaction was terminated by adding a premixture of n-butanol (40.0 g) and DMEOA (0.19 g), and then the temperature was cooled to 40°C. The viscosity of the product was 2,567 cps. The liquid product exhibited slight gelling behavior.

[0174] Example 5

[0175] Another conventional phenolic varnish resin was functionalized as follows: At ambient temperature, n-butanol (70.0 g), dibutoxymethane (Sigma-Aldrich) (80.6 g), and phenolic varnish resin (Alnovol PN320, Allnex) (85.0 g) were added to a one-liter four-necked round-bottom flask equipped with a mechanical stirrer, nitrogen inlet, reflux condenser, Dean-Stark receiver, and thermocouples connected to the heating control and heating devices. The phenolic varnish resin was dissolved in n-butanol and dibutoxymethane at 65°C to form a clear yellow solution. Sulfuric acid (98%, 0.22 g) was added to the flask. The reaction mixture was heated and maintained at 85°C for approximately 4 hours until the solubility of the sample in the test solution was less than 1% by weight. The product was a clear, deep orange liquid. The viscosity was 292 cps, the solids content was 39.9%, and the free formaldehyde was less than 0.01%.

[0176] Example 6

[0177] Four different coated substrates were prepared using the resin sample from Example 1 and dibutoxymethane (DBM) from Example 2, and formulated as shown in Table 2 below. The solutions were applied to tinplate (ETP) at a wet coating thickness of approximately 4 mg / s² to approximately 6 mg / s², and baked at 400℉ for approximately 5 minutes. The baked samples were then immersed in methyl ethyl ketone (MEK) at ambient temperature (RT) for 60 minutes. If the sample remained in a hard solid form in MEK, the sample was fully cured. If the sample became a soft, swollen form in MEK, the sample was partially cured. Uncured samples were completely or substantially dissolved in MEK. The results are provided in Table 2.

[0178] Table 2. Preparation of Phenolic Compounds and DBM

[0179]

[0180] Example 7

[0181] As shown in Table 3 below, twelve different coating substrates were formulated using dibutoxymethane (DBM) (Sigma-Aldrich) and a sulfuric acid catalyst. The solutions were applied to tinplate (ETP) at a wet coating weight of approximately 4 mg / sq. inch to approximately 6 mg / sq. inch and baked at 400°F for 5 minutes. The baked samples were then immersed in MEK at ambient temperature for 60 minutes. If the sample remained in a hard solid form in MEK, it was considered fully cured. If the sample became a soft, swollen form in MEK, it was considered partially cured. Uncured samples were completely or mostly dissolved in MEK. The results are presented in Table 3 below.

[0182] Table 3. Preparation of Phenolic Compounds and DBM

[0183]

[0184] Example 8

[0185] As shown in Table 4, two different coating substrates were prepared using conventional phenolic varnish resin, DBM for functionalization, and sulfonic acid. The solution was applied to tinplate (ETP) at a wet coating weight of approximately 4 mg / s² to approximately 6 mg / s², and baked at 400℉ for 5 minutes. The baked samples were then immersed in MEK at ambient temperature for 60 minutes. In Table 4 below, Cycat 600 (Cytec), an aromatic sulfonic acid catalyst, was used; and Nacule 5929 (KingIndustries), a latent aromatic sulfonic acid catalyst, was also used. If the sample remained in a hard solid form in MEK, the sample was fully cured. If the sample became a soft, swollen form in MEK, the sample was partially cured. Uncured samples were completely or substantially dissolved in MEK. The results are provided in Table 4 below.

[0186] Table 4: Preparation of Phenolic Compounds and DBM

[0187]

[0188] Example 9

[0189] This example compares the stability of a functionalized phenolic varnish resin prepared by reacting Alnovol PN 320 (e.g., Alnovol PN 320 from Allnex (a conventional phenolic varnish)) with DBM as shown in Example 5. This functionalized phenolic varnish resin has a solids content of approximately 37.5%, a viscosity of 81 cp, and a number-average molecular weight of approximately 1,040 g / mol. Table 7 provides the stability.

[0190] Table 7: Viscosity stability after 90 days at ambient temperature

[0191]

[0192] In the cases of samples 1, 2, and 4, the reaction of conventional phenolic varnish PN 320 with DBM or formaldehyde with H2SO4 catalyst ceased when the solubility endpoint was reached. Sample 1 was good when fresh but gelled after 90 days because it was not neutralized (e.g., pH < 0). Sample 2 did not gel, but its viscosity increased by more than 100% because it was not completely neutralized (e.g., pH < 1). For sample 3, the reaction of conventional phenolic varnish (e.g., PN320) with DBM and H2SO4 continued for an hour after the solubility endpoint was reached. Fresh sample 3 had a much higher initial viscosity than the other samples, and the sample was also not neutralized. Therefore, it gelled during a short aging period at ambient temperature. Sample 4 was completely neutralized with common neutralizing agents (e.g., sodium hydroxide, potassium hydroxide, etc.) (e.g., pH > 4) and remained stable without an increase in viscosity.

[0193] Example 10

[0194] This example compares the curing of functionalized phenolic varnish resins obtained from conventional phenolic varnish resins (e.g., Alnovol PN320, a conventional phenolic varnish from Allnex) under MEK dual-friction conditions. Conventional phenolic varnish resins are either pre-reacted with dibutoxymethane or reacted in situ with dibutoxymethane (DBM) in a coating composition containing a second polymer. Coated samples on tinplate were baked at 400℉ for 10 minutes to achieve 4 mg / inch. 2 Up to 6 mg / inch 2 The dry coating weight. Table 8 provides the MEK double friction (where the numbers in parentheses reflect that the MEK double friction was achieved by immersion in MEK for 20 minutes at room temperature).

[0195] Table 8: MEK Two-Friction

[0196]

[0197] Example 11

[0198] The first resin samples A and B of the present invention (pre-reacted or blended samples, respectively) from Example 10 were further analyzed with the second polymers of acrylic acid, polyester, and epoxy. The time (in minutes) required to reach 63% total curing was determined using DMA analysis and compared with a control polymer of methyl phenolic resin without samples A or B. As described in Example 10, the compositions were cured at 400℉ for 10 minutes. The results are provided in Table 9 below, showing that the curing conditions were comparable among the samples.

[0199] Table 9

[0200]

[0201] Example 12

[0202] The modulus growth of the phenolic varnish blends and the pre-reacted first resin of the present invention in Examples 10 and 11 was further evaluated using DMA analysis and compared with MEK bifriction in the HEMA acrylic composition of Example 8. The coated samples were cured as described in Example 9. The storage modulus of the coated samples was evaluated using DMA analysis and MEK bifriction. The storage modulus is provided in... Figure 1 In addition, MEK dual friction is provided in Table 9 below.

[0203] Table 10: MEK Two-Friction

[0204]

[0205] All patents, patent applications, and publications cited herein, including their full disclosures and electronically available materials, are incorporated herein by reference. The foregoing detailed descriptions and embodiments are given solely for clarity of understanding. It should be understood that no unnecessary limitations are intended. The invention is not limited to the exact details shown and described, and variations that will be apparent to those skilled in the art will be included within the scope of the invention as defined by the claims.

Claims

1. A food or beverage container coating composition, said food or beverage container coating composition comprising: Self-crosslinking phenolic varnish resin; The second polymer is capable of participating in the crosslinking reaction with the self-crosslinking phenolic varnish resin; Optionally, a water-based or solvent-based liquid carrier; and The food or beverage container coating composition comprises, by weight, an excess of the second polymer relative to the self-crosslinking phenolic varnish resin.

2. The food or beverage container coating composition according to claim 1, wherein the self-crosslinking phenolic varnish resin is a functionalized phenolic varnish resin, preferably a functionalized phenolic varnish resin having a protected substituent hydroxymethyl group, and most preferably, the protected substituent hydroxymethyl group comprises an alkoxymethylene substituent.

3. The food or beverage container coating composition according to claim 2, wherein the functionalized phenolic varnish resin is a reaction product comprising: (i) a phenolic varnish resin (e.g., a phenolic compound reacted with an aldehyde, preferably formaldehyde, under acidic conditions) and any of the following substances: (ii)(a) an aldehyde, preferably formaldehyde, and a monohydric alcohol (preferably n-butanol) or glycol ether, using an acid catalyst, or (ii)(b) a reactive solvent, including dialkoxymethane, preferably dibutoxymethane, and preferably using an acid catalyst.

4. The food or beverage container coating composition according to claim 3, wherein the dialkoxymethane of the reactive solvent has the structure of formula I: (Equation I) in R1 and R2 are independently C1 to C10 alkyl groups, C1 to C10 alkyl ether groups (e.g., alkyl groups in which one or more carbon atoms are replaced by oxygen atoms), preferably C1 to C6 alkyl groups, more preferably C2 to C5 alkyl groups, and most preferably C4 alkyl groups; and Each R3 is independently hydrogen or a C1 to C6 alkyl group, and preferably each R3 is hydrogen.

5. The food or beverage container coating composition according to claim 3 or 4, wherein the dialkoxymethane of the reactant solvent has a boiling point of at least about 88°C and preferably about 170°C to about 305°C, and preferably, wherein the dialkoxymethane is dibutoxymethane.

6. The food or beverage container coating composition according to claim 3, wherein (i) the phenolic varnish resin is formed by reacting the phenolic compound and the aldehyde under acidic conditions (e.g., pH of about 2 or less, and preferably, pH of about 2 to about -2), wherein the phenolic compound is in molar excess relative to the aldehyde (e.g., the molar ratio of the phenolic compound to the aldehyde is greater than 1, and preferably about 1 to about 3), thereby forming a phenolic varnish intermediate, and wherein the phenolic varnish intermediate is further reacted with any of the following substances: (ii)(a) the aldehyde, preferably formaldehyde and the monohydric alcohol (preferably n-butanol) or the glycol ether, or (ii)(b) the reactive solvent, including the dialkoxymethane.

7. The food or beverage container coating composition according to any of the preceding claims, wherein the functionalized phenolic varnish resin is a polymer or oligomer having the structure of Formula II: (Formula II) R4 is a C1 to C10 alkyl group or a C1 to C10 alkyl ether group (e.g., an alkyl group in which one or more carbon atoms are replaced by oxygen atoms), and preferably a C1 to C6 alkyl group, more preferably a C2 to C5 alkyl group, and most preferably a C4 alkyl group.

8. The food or beverage container coating composition according to any of the preceding claims, wherein the number-average molecular weight of the functionalized phenolic varnish resin is greater than about 500 g / mol (preferably greater than about 1,000 g / mol), and more preferably less than about 4,000 g / mol (most preferably less than 3,000 g / mol), as measured by gel permeation chromatography (GPC) using polystyrene standards.

9. The food or beverage container coating composition according to any of the preceding claims, wherein the phenolic compound is phenol, cresol, resorcinol, xylenol, tert-butylphenol, cyclohexylmethylphenol, dicyclopentadiene, vinylphenol, aminophenol, methoxyphenol, naphthol, cashew nut shell phenol, cashew nut biphenol, or a combination thereof, and preferably phenol.

10. The food or beverage container coating composition according to any of the preceding claims, wherein the aldehyde is formaldehyde, acetaldehyde, propionaldehyde, paraformaldehyde, butyraldehyde, glyoxal, trioxane (e.g., a trimer of formaldehyde), hydroxybenzaldehyde (including any isomer), furfural, furfural, or a combination thereof, and preferably formaldehyde.

11. The food or beverage container coating composition according to any of the preceding claims, wherein the main chain of the functionalized phenolic varnish resin comprises a hydrocarbon-bridged aromatic group having an alkoxymethylene substituent, and wherein the molar ratio of dialkoxymethane to conventional phenolic varnish resin (e.g., dialkoxymethane / phenolic varnish) is at least about 0.07, at least about 0.2 in other methods, at least about 0.4 in other methods, and at least about 0.6 in yet another method.

12. The food or beverage container coating composition according to claim 11, wherein the hydrocarbon bridge is a methylene group.

13. The food or beverage container coating composition according to claim 11 or 12, wherein the main chain does not contain ether bridges between aromatic groups.

14. The food or beverage container coating composition according to any of the preceding claims, wherein the second polymer comprises a polyether polymer, polyester polymer, acrylic polymer, polyolefin polymer, or copolymer thereof having hydroxyl groups (preferably primary hydroxyl groups) and / or carboxyl groups for reacting with a self-crosslinking phenolic varnish resin.

15. The food or beverage container coating composition according to any of the preceding claims, wherein the acid value of the second resin is at least about 0 mg KOH / g resin, and preferably about 0 mg KOH / g resin to about 150 mg KOH / g resin.

16. The food or beverage container coating composition according to any of the preceding claims, wherein the second resin has a hydroxyl value of at least about 15 mg KOH / g resin, and preferably about 20 mg KOH / g resin to about 200 mg KOH / g resin.

17. The food or beverage container coating composition according to any of the preceding claims, wherein the food or beverage container coating composition is substantially free of each of bisphenol A and bisphenol S (and preferably free of either of them).

18. A food or beverage container coating composition according to any of the preceding claims, wherein the neutralized self-crosslinking phenolic varnish resin (e.g., pH greater than 4.0) is stable at room temperature (e.g., from about 20°C to about 25°C) for at least about 90 days, wherein the viscosity change is an increase in viscosity of less than 100% relative to the viscosity at time T0, and preferably, the viscosity change is an increase in viscosity of about 0% to less than 50% relative to the viscosity at time T0, wherein the viscosity is measured according to ASTM D2983.

19. The food or beverage container coating composition according to any of the preceding claims, wherein the coating composition is applied to tinplate (ETP) and cured at 200°C for 10 minutes to achieve 4 mg / in 2 Up to 8mg / in 2 At the dry film thickness, measured according to ASTM D5402, it exhibits at least approximately 50 MEK double friction cycles.

20. A food or beverage container coating composition according to any of the preceding claims, wherein the coating composition comprises about 5% to about 50% by weight of the self-crosslinking phenolic varnish resin (preferably about 15% to about 35% by weight of the self-crosslinking phenolic varnish resin) and about 50% to about 95% by weight of the second polymer (preferably about 60% to about 80% by weight of the second polymer) based on total resin solids.

21. The food or beverage container coating composition according to any of the preceding claims, wherein, based on the total resin solids comprising the self-crosslinking phenolic varnish resin, the coating composition comprises about 5% to about 35% by weight of the reactive solvent, including the dialkoxymethane.

22. The food or beverage container coating composition according to any of the preceding claims, wherein the coating composition contains less than about 1,000 ppm of free formaldehyde, preferably less than 500 ppm of formaldehyde, and most preferably less than 100 ppm of free formaldehyde.

23. The food or beverage container coating composition according to any of the preceding claims, wherein the food or beverage container coating composition further comprises a lubricant.

24. The food or beverage container coating composition of claim 23, wherein the lubricant is selected from carnauba wax, polyvinyl wax, Fischer-Tropsch wax, fatty acid ester wax, silicone wax, lanolin wax, hydroxyl-functional polysiloxane wax, or combinations thereof.

25. The food or beverage container coating composition according to any of the preceding claims, wherein the coating composition contains at least about 25% by weight of water.

26. The food or beverage container coating composition according to any of the preceding claims, wherein the coating composition further comprises one or more water-miscible organic solvents.

27. The food or beverage container coating composition of claim 26, wherein the water-miscible organic solvent comprises isopropanol, ethanol, methanol, butanol, pentanol, glycol, glycol ether, glycol ester, acetone, methyl ethyl ketone, tetrahydrofuran, or mixtures thereof.

28. The food or beverage container coating composition according to claim 26 or 27, wherein the coating composition comprises about 3.5% to about 15% by weight of the one or more water-miscible organic solvents.

29. The food or beverage container coating composition according to any of the preceding claims, wherein the coating composition comprises at least about 5% by weight of one or more organic solvents.

30. The food or beverage container coating composition according to any of the preceding claims, wherein, when tested according to a total extraction test, the food or beverage container coating composition forms a cured coating containing less than 50 ppm of extractable material, if applicable.

31. The food or beverage container coating composition according to any of the preceding claims, wherein the food or beverage container coating composition comprises about 15% to about 40% by weight of total resin solids (preferably about 18% to about 35% by weight, and more preferably about 20% to about 30% by weight).

32. An article comprising a food or beverage container or a portion thereof, the article comprising: Metal substrate; and A thermosetting coating disposed on at least a portion of the metal substrate, wherein the thermosetting coating is derived from a food or beverage coating composition according to any one of claims 1 to 31.

33. The article of claim 32, wherein the thermosetting coating is formed by baking the food or beverage coating composition of any one of claims 1 to 31 at a temperature of at least about 135°C.

34. The article of claim 32 to 33, wherein the food or beverage coating composition is applied to the food or beverage contact surface of the metal substrate.

35. A method for forming a food or beverage container, the method comprising: Provide a food or beverage coating composition according to any one of claims 1 to 31; as well as The food or beverage coating composition is applied to the metal substrate or a portion thereof before or after the metal substrate is formed into a food or beverage container or a portion thereof.

36. The method of claim 35, further comprising baking and curing the food or beverage coating composition after it has been applied to the metal substrate.

37. A method comprising applying a coating composition according to any one of claims 1 to 31 to a metal substrate of a food or beverage container or a portion thereof.

38. The method, article, or food or beverage container coating composition according to any of the preceding claims, wherein when the food or beverage container coating composition is applied to tinplate and baked at 400℉ for 10 minutes to achieve 4 mg / inch. 2 Up to 6 mg / inch 2 When measured using DMA analysis as described herein, the time required to achieve 63% curing at the dry coating weight is approximately 115 minutes or less, approximately 50 minutes or less, approximately 20 minutes or less, approximately 15 minutes or less, or approximately 10 minutes or less.

Citation Information

Patent Citations

  • Tapered metal cup and method of forming the same

    US10875076B2

  • Metal packaging powder coating compositions, coated metal substrates, and methods

    US11248127B2

  • Coating compositions including a polyester, articles, and methods of coating

    US11827803B2

  • Compositions for Containers and Other Articles and Methods of Using Same

    US20130206756A1

  • Compositions for Containers and Other Articles and Methods of Using Same

    US20130316109A1